Modular depressant constructed via MA-linker assembly: Dual functionality in selective inhibition and aggregation of serpentine during the flotation of pyrite - Heng Zhang; Zhi Lei; Hao Tang; Hao-Ran Wu; Xu-Gang Zhang; Peng-Fei Xu (Minerals Engineering, 2026)

Lipid-lowering activity of mulberry seed unsaturated fatty acids: integrating network pharmacology and experimental validation - Yue Zhang; Haoran Huang; Jianglong He; Yuqi Li; Xueping Jiang; Ping Wu; Syed Asim Shah Bacha; Ran Zhang; Hao Li; Gaiqun Huang; Zhongzheng Gui (Functional & Integrative Genomics, 2026)

Bacterial surface interfaces in food systems: a programmable regulatory layer - Hao-Ran Zhang; Jun Meng; Yun-Peng Hao; Jing-Qian Song; Xiao-Yue Wang; Jing-Yi Yang; Zai-Chen Li; Jun Xi; Chang-He Ding; Tong Li (Trends in Food Science & Technology, 2026)

Mixing with T. chinensis and P. bournei reshapes microbial function and soil-plant nutrient status in chinese fir plantations at huapo forest farm Guizhou - Kai Yao; Bo Ran; Aoli Zhang; Yunhui Wu; Hao Zhang; Yang Yang (Forest Ecology and Management, 2026)

Meteorology-driven long-range transport to an ultra-low emission region: a case study of Hainan during the monsoon - Hao Guo; Yanli Zhang; Haofan Ran; Xinming Wang (Atmospheric Environment, 2026)

RETRACTED: Metastable conformational regulation in heat-induced gluten aggregation: multiscale experiments and molecular dynamics reveal distinct roles of HMW-GS at the Glu-B1 locus - Bo Wang; Ping-ping Zhang; Rong-ran Zhang; Tian Lv; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Xin-long Dai; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Synergistic stabilization of a clean-label bigel: whey protein isolate constructing dual oleogel/hydrogel networks - Run-Hao Fu; Han Tao; Bao-Cai Xu; Ran Feng; Bao Zhang (Food Hydrocolloids, 2026)

Trace ammonia-assisted binary solvothermal etching for highly stable micron-sized porous silicon/carbon anodes - Fenghui Li; Qian Zhang; Hao Wu; Ping Li; Zhanyong Guo; Ran Zhang; Lianbang Wang (Chemical Engineering Journal, 2026)

Probiotic Bacillus strains enhance cellulose digestibility and silkworms growth via gut microbiota modulation - Yueqin Jin; Ying Zhao; Chen Chen; Xueping Jiang; Sitong Chen; Ran Zhang; Hao Li; Zhongzheng Gui (Journal of Insect Physiology, 2026)

Experimental investigation on seismic performance evolution of reinforced concrete columns considering spatially differential corrosion - Yang Liu; Wei-Ping Zhang; Qian-Qian Yu; Hao-Ran Zuo; Xiang-Lin Gu (Engineering Structures, 2026)

Effects of wastewater flow direction on sulfur-based autotrophic denitrification processes: operational patterns, denitrification performance and response mechanisms - Daheng Ren; Heng Dong; Wenke He; Zhiqiang Zuo; Xiangli Zeng; Xuchen Ba; Yang Yu; Haoran Xu; Guijiao Zhang; Ran Zeng; Jiamin Xu; Na Zhang; et al. (Chemical Engineering Journal, 2026)

Soil quality evaluation of no-tillage reseeding grassland based on quality index area and sensitivity-resistance method - Xiaoqing Qiu; Shuang Yan; Hao Shi; Fei Xia; Wei Wei; Yu Zhang; Jiarui Ding; Jiayu Cao; Haoyang Wu; Linling Ran; Jinglong Wang; Junqiang Wang (Applied Soil Ecology, 2026)

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

From interfacial stabilization to maintainable operation: fouling-resilient synthetic urine valorization by bipolar membrane electrodialysis - Hao-Ran Yang; Yu Xin; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Yuan Liu (Water Research, 2026)

Bi-objective optimization of 3D track layout for railway humps: rolling efficiency and construction cost - Wei Li; Yang Ran; Hao Pu; Xinjie Wan; Paul Schonfeld; Shaoxiang Huang; Shicheng Zhang (Swarm and Evolutionary Computation, 2026)

Volatile methylsiloxanes in a textile dyeing and printing industrial park: Source profiles, ambient distributions and SOA formation potential - Xiaodie Pang; Hao Han; Wei Song; Xiangyu Zhang; Ran An; Jianqiang Zeng; Chao Peng; Weiqiang Yang; Chenshuo Ye; Xiao Tian; Hongcheng Lu; Zhou Zhang; et al. (Journal of Hazardous Materials, 2026)

Retraction notice to “Metastable conformational regulation in heat-induced gluten aggregation: multiscale experiments and molecular dynamics reveal distinct roles of HMW-GS at the Glu-B1 locus” [Food Hydrocolloids 179 (2026) 112791] - Bo Wang; Ping-ping Zhang; Rong-ran Zhang; Tian Lv; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Xin-long Dai; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Asymmetric spectral modulation of bioinspired Janus metafabric toward environment-adaptive thermal and moisture management under extreme conditions - Yang Wu; Long Zhang; Hao-Ran Yang; Jiaqi Li; Yuzhen Hou; Chang-Shun Li; Bobo Shi; Meng Zhou; Wulin Shang; Weiqing Kong; Huan Xu; Gang Zhou; et al. (Chemical Engineering Journal, 2026)

Mitogenome assembly of the floating-leaved aquatic plant Nymphoides peltata provides insights into organellar evolution and aquatic adaptation in Asterales - Rui Dong; Meng-Na Yu; Lei Zhang; Si-Hao Wang; Xi-Ran Tong; Zhi-Zhong Li (Hydrobiologia, 2026)

Aboveground inputs rather than belowground root drive SOC responses to long term N addition in alpine grassland ecosystems of Qinghai-Tibetan Plateau - Ran Zhang; Hao Shen; Shikui Dong; Qiang Yu; Juejie Yang; Ying Li; Yaoming Li; Jiannan Xiao; Shuai Li; Hui Zuo; Hang Shi; Fengcai He; et al. (Agriculture, Ecosystems & Environment, 2026)

A genetic clash of sister groups: first-ever intergeneric and interspecific mitogenome comparisons between two close gall midge genera (Cecidomyiidae: Cecidomyiinae: Cecidomyiini): the floral and veggie-versatile Contarinia and the mango-mad Procontarinia, with phylogenetic applications - Xiu-Fang Dong; Yi-Fan Zhang; Xu-Yuan Gao; Ning-Bo Ma; Yu Ji; Yan-Fei Li; Yi-Ran Mu; Zheng-Hao Yue; De-Wei Wei; Yong-Hao Yu; Hai-Li Qiao; Wen-Jun Bu; et al. (Arthropod-Plant Interactions, 2026)

Single-cell transcriptomic analysis identifies a MIF-driven keratinocyte-macrophage-Th2 axis as a key inflammatory circuit in atopic dermatitis - Yan Wei; Rui-Min Bai; Hao-Ran Guo; Jin Shan; Li-Juan Wang; Yan Zhou; Kuan-Hou Mou; Yan Zheng; Ya-Guang Zhang (Inflammation Research, 2026)

Novel photoelectron-driven nitrate reduction in anammox granules using photosensitive semiconductor iron mineral for wastewater treatment - Xue Wang; Tao Xue; Jian Li; Caiyun Zhang; Guizhen Hao; Yuzi Xing; Ran Tao; Lin Guo; Haozhe Zhang; Shu Chai; Lei Zheng (Water Research, 2026)

Effect of overlying low-permeable soil on underwater shield tunnel response to water level fluctuation - Dong-Mei Zhang; Hao-Ran Lai; Yi-Yao Shen; Feng Du (Tunnelling and Underground Space Technology, 2026)

Enhanced dimethylsulfide emissions following eutrophication remediation in a coastal bay: biogeochemical and hydrological controls - Xiao-Ran Li; Jin-Wei Wu; Xiao-Song Zhong; Hao Qiao; Shi-Bo Yan; Feng Xu; Yu-Cheng Jiang; Rui-Te Zhang; Yu-Hao Qiu; Hong-Hai Zhang (Progress in Oceanography, 2026)

Permian A-type felsic magmatism in the South Tianshan Orogenic Belt: Crustal melting triggered by the Tarim mantle plume - Zhi-Hao Song; Xian-Tao Ye; Xiao-Qiang Liu; Hong-Ran Wang; Ming-Can Yang; Shun-Hao Fu; Chuan-Lin Zhang (Lithos, 2026)

Exogenous microbial agents interact with housefly larvae to reshape the microbiome and accelerate cellulose degradation in silkworm (Bombyx mori) excrement - Chen Chen; Yuanhao Zhang; Yueqin Jin; Jieling Zhou; Xueping Jiang; Sitong Chen; Ran Zhang; Hao Li; Zhongzheng Gui (Journal of Insect Physiology, 2026)

Phage tail Fiber-based electrochemical biosensor for rapid detection of Cronobacter spp. in food - Hao Hu; Xiangmu Yang; Shaowen Guo; Jing Wang; Tao He; Ran Wang; Lili Zhang; Heye Wang (Food Research International, 2026)

Lipid profile of sheep milk and its impact on taste: a combination study of lipidomics and electronic tongue - Hao Yuan; Zhongshi Zhu; Yuxin Wang; Chang Chen; Haozhan Liu; Ran Li; Liwei Zhang; Yuxuan Song (Food Research International, 2026)

Metal-air fuel cells for phosphorus recovery from wastewater: A critical analysis of principles, progress, and application perspectives - Lin-Jiang Zhong; Di Wu; Meng-Yue Zhang; Shu-Jie Hu; Hao-Ran Yang; Yuan Liu (Chemical Engineering Journal, 2026)

Joule heating-driven chemical looping dry reforming of CH4 and CO2 over monolithic LaFeO3/Ti wire oxygen carrier - Kun Wang; Haoyu Qi; Shengnan Zhao; Zezhou Ran; Hao Zhang; Kunlun Li (Chemical Engineering Journal, 2026)

A self-perpetuating cycle: how heavy metals shape DOM chemistry to promote their own immobilization in soil - Shuyi Zhang; Wenjun Zhang; Ye Li; Longfei Zhao; Chunmei Ran; Hongming Cai; Zhineng Hao; Junjie Zhang; Lei Wang (Environmental Monitoring and Assessment, 2026)

Hydraulic performance of circular tunnels with interior drainage boundaries subjected to water level fluctuation - Hao-Ran Lai; Dong-Mei Zhang; Yi-Yao Shen; Bin-Lin Gan (Transportation Geotechnics, 2026)

Construction of Li1-xMn2O4-Pb composite electrode ESIX system for efficient lithium recovery from high-sodium sulfate-type lithium-precipitation mother liquor - Jialu Chen; Jiang Gao; Ran Zhang; Zirui Wang; Qiang Ren; Fengfeng Gao; Zhonglin Zhang; Xiao Du; Xiaogang Hao (Journal of Environmental Chemical Engineering, 2026)

Ion-specific multiscale regulation of gelatinization and retrogradation in normal and waxy wheat starches: Cooperative roles of valence, hydration, and molecular chain architecture - Tian Lv; Xin-rong Lv; Shu-ning Yuan; Yu Hu; Rong-ran Zhang; Yue Zhang; Chuan Zhong; Pei Wang; Qin Zhou; Dong Jiang; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Structure-Constrained Prior Ensembles for ES-MDA Post-Stack Acoustic Impedance Inversion - Zhi-fang Ran; Yin-quan Hao; Pin Zhang; Weiwei Gu; Guo-fa Li (Applied Geophysics, 2026)

Genome wide association analysis and association of genetic risk and lifestyle with upper gastrointestinal cancer among an endoscopy-screened cohort in China - Feifan He; Xianhui Ran; Hao Jiang; Zhiyuan Fan; Yueying Zhang; Jinwu Wang; Changqing Hao; Guohui Song; Yanwei Gong; Yanyan Li; Xinqing Li; Ru Chen; et al. (Science Bulletin, 2026)

Unlocking the effects of cold plasma on enhancing the stabilization of oat flour: Insights from storage characteristics, lipidomics, and flavor analysis - Shunzhang Ma; Hao Ran; Jinquan Lin; Yuanlin Sun; Lizhen Zhang; Fang Zhong; Sumei Zhou; Dianzhi Hou (Journal of Stored Products Research, 2026)

Ligand-specific tuning of an olfactory receptor to respond to sex pheromones in cowpea weevil, Callosobruchus maculatus - Hao-Ran Lu; Shan Li; Li-Jie Zhang; Kai Shi; Si-Qin Ge; Zhen Zou (Insect Biochemistry and Molecular Biology, 2026)

Realistic-NPs trigger depression-like behaviors via mitochondrial iron overload mediating ferroptosis - Han Hao; Fan Shi; Ran Tian; Licheng Yan; Bingrui Liu; Cunbao Ding; Weixuan Wang; Yanshu Zhang (Chemico-Biological Interactions, 2026)

Herbiconiux dendrobii sp. nov., a Novel Bacterium Isolated from Dendrobium devonianum Sawdust Substrate - Hao Liang; Fang Zhao; Hong-Bo Zha; Zhang-Gui Ding; Le-Le Li; Jiang-Yuan Zhao; Zhi-Ran Zhao; Min Zheng; Jian-Sheng Cheng; Hui-Cheng Deng; Shu-Kun Tang; Ming-Gang Li (Current Microbiology, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Multifaceted regulation of immune cells in radiation-induced pulmonary fibrosis: from mechanistic insights to targeted therapies - Li Shen; Wanrong Zhang; Yonghao Yang; Zhiqiang Du; Shiyan Fu; Feng Huang; Xiaoyu Yang; Juan Li; Yonghong Ran; Yuhui Hao (Inflammation Research, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

A multi-component recycling strategy for photovoltaic waste: Co-recovering silicon and PVDF into Ag–F reinforced Si/C anodes - Yihao Li; Yiqing Chen; Xiaojiao Zhang; Yaoguang Guo; Shuai Chen; Jie Yang; Tie Lin; Haodong Ran; Yang Zhang; Qin Xu; Yanlin Wu; Hao Yuan; et al. (Resources, Conservation and Recycling, 2026)

The transcriptional regulatory module MdERF2-MdSCR11 promotes ABA-mediated apple fruit ripening through synergistic repression of MdABA4-2 - Miaomiao Wang; Qizhe Li; Hao Wang; Nan Jiang; Jiale Wang; Xiaotong Hu; Yu Liu; Tuanhui Bai; Jian Jiao; JiangLi Shi; Ran Wan; Kunxi Zhang; et al. (Postharvest Biology and Technology, 2026)

Embryonic Proto-Tethys Ocean: Evidence from the early Ediacaran Kuyake ophiolite mélange along the Altyn Tagh in NW China - Hong-Ran Wang; Chuan-Lin Zhang; Hua-Dong Ma; Yan Jing; Masumeh Sargazi; Zhi-Hao Song (Precambrian Research, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Strategy for optimization of auto-driven electrochemical module towards phosphorus recovery from wastewater: Performance and mechanism of electric field regulation - Lin-Jiang Zhong; Di Wu; Meng-Yue Zhang; Shu-Jie Hu; Hao-Ran Yang; Ying Chen; Qi Kuang; Yuan Liu (Journal of Cleaner Production, 2026)

Antibacterial effect of the endolysin LysMD10 combined with citric acid against Salmonella and its application for eggshells decontamination - Hao Ding; Kaiyuan Huang; Tao Wang; Junjie Xu; Lichang Sun; Xinyi Zhang; Jiayuan Du; Xinxin Yang; Pengfei Gao; Bowen Liu; Hongduo Bao; Ran Wang; et al. (Food Control, 2026)

Calcium-mediated modulation of ultra-low-ester pectin-gluten interactions: subunit-level mechanisms revealed using HMW-GS deletion lines and molecular dynamics simulations - Rong-ran Zhang; Ping-ping Zhang; Tian Lv; Bo Wang; Zhe Liu; Yue Zhang; Chuan Zhong; Pei Wang; Qin Zhou; Dong Jiang; Hao Jiang; Tao Yang (Carbohydrate Polymers, 2026)

Overexpression of PtrPYL11 enhance drought tolerance in Populus: evidence from genome-wide identification and comparative transcriptome profiling - Shuang-Lian Deng; Shu-Ying Wei; Rui-Quan Wang; Yuan Zhang; Hao Li; Xing-Yu Liu; Xin-Ran Yu; Guan-Ru Ren; Ting Wang; Fang He (Plant Cell Reports, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

Research on a complex start-up control strategy for power-shift tractors based on rule mapping and multi-mode model predictive control - Li-Quan Lu; Ze-Peng Zhang; Guang-Lin Zhang; Hao-Ran Yang; Zhong-Xiang Zhu; Zheng-He Song; Zhi-Qiang Zhai; Jian-Hua Wang; Chuan-Chuan Zhang (Computers and Electronics in Agriculture, 2026)

Physicochemical strategies for antibiotic removal in aquaculture wastewater: Mechanistic insights, technological challenges, and sustainable development pathways - Tai-Yue Wang; Yan-Ping Qiao; Kai-Jun Yue; Ming Cheng; Li-Ting Hao; Nan Zhang; Ran-Bin Liu; Chen Shi (Aquaculture, 2026)

AnchorReF: A novel anchor-based visual re-localization framework aided by multi-sensor data fusion - Hao Wu; Yu Ran; Xiaoxiang Zhang; Xinying Luo; Li Wang; Teng Zhao; Yongcheng Song; Zhijun Zhang; Huisong Zhang; Jin Liu; Jian Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Structural and textural enhancement of oleogels via l-lysine-mediated whey protein cryogel modification - Run-Hao Fu; Ran Feng; Si-jie Wu; Bao-Cai Xu; Bao Zhang (Food Chemistry, 2026)

Uncovering pH-driven metastable transitions and thermal aggregation of HMW-GSs via all-atom molecular dynamics simulations - Tao Yang; Rong-ran Zhang; Xin-rong Lv; Tian Lv; Bo Wang; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Zhe Liu; Hao Jiang (Food Hydrocolloids, 2026)

Seismic data processing key technology for coalbed methane reservoir - Ming Zhang; Bao-yin Zhao; Zhi-fang Ran; Wen-wu Shi; Hao Li; Kai-long Wu; Gen-yang Tang (Applied Geophysics, 2026)

A multifunctional 5-fluorouracil prodrug: synthesis, biological evaluation, and antitumor mechanism investigation - Ran Zhang; Liqing Tang; Jianglong He; Guanyu Jiang; Yingfei Su; Xueping Jiang; Ping Wu; Dongyang Zhang; Sitong Chen; Hao Li; Zhongzheng Gui (Molecular Diversity, 2026)

Bioinformatics-based discovery of a new norsesquiterpenoid from agarwood targeting CHRM2 and regulating the PI3K-Akt pathway in liver cancer - Zi-Xiao Jiang; Jian Feng; Wen-Cheng Hou; Mei-Ran Wang; Shu-Nan Zhang; Hao-Jie Liang; Yang-Yang Liu (Phytochemistry Letters, 2026)

Warming-driven and depth-dependent responses of soil microbial communities toward nutrient limitations: Ecological insights into alpine grassland restoration - Hao Shi; Wei Wei; Jun-qiang Wang; Fei Xia; Cai-hong Yang; Lin-ling Ran; Yun-yin Xue; Hao-yang Wu; Shuang Yan; Yu Zhang; Shai-kun Zheng; Xiao-qing Qiu (Applied Soil Ecology, 2026)

Low N Deposition Coupled With Climate Warming Promote Soil Asymbiotic N Fixation via Increasing Microbial Specialists in Alpine Grassland - Ke Zhang; Yaoming Li; Ran Zhang; Anna Du; Zuyan Ma; Hang Shi; Juejie Yang; Wenli Ding; Hao Shen; Richard D. Bardgett; Huaiying Yao; Shikui Dong (Global Change Biology, 2026)
Biological nitrogen fixation (BNF) is a vital process for introducing new N into natural ecosystems, and this process has been demonstrated to be suppressed by high N deposition. However, the net ecological effect and underlying mechanisms of BNF under chronic low‐level N deposition, characteristic of terrestrial ecosystems, remain highly uncertain. Given that climate warming is a key environmental change factor concurrent with N deposition, it is important to investigate whether climate warming can change BNF activity and alter the effects of N deposition on BNF. To fill these knowledge gaps, we implemented a decade‐long‐term manipulation experiment in an alpine grassland ecosystem with 5 treatments, that is, experimental warming (W), low‐level N deposition (N L ), high‐level N deposition (N H ), combination of climate warming and low‐level N deposition (WN L ) and the control (CK). BNF rate was measured by 15 N 2 isotope discrimination. We found that N L significantly stimulated BNF by 112%, contrasting sharply with the complete suppression under N H . Climate warming alone increased the BNF rate by 123%, while the WN L amplified this effect, stimulating BNF by 234%. Structural equation modeling revealed that WN L selectively favored specific diazotrophic groups ( Desulfovibrio ), whose proliferation directly drove the observed BNF shifts. In this N‐limited alpine grassland, low‐level chronic N deposition, especially when combined with warming, fundamentally shifts the diazotrophic community structure by driving a process of niche contraction. This selection process functionally enriches specialized diazotrophs, resulting in a dramatic, positive feedback that significantly promotes the overall biological nitrogen input. Our findings highlight the potential for increased N inputs under realistic future climate scenarios and provide a scientific basis for precision N management in alpine grasslands, both on the Qinghai‐Tibetan Plateau and worldwide.

Study on the Applicability of Intelligent Recognition Algorithms to Different Types of Subgrade Defects - Yu-xuan Han; Yan-li Qi; Yi Zhang; Yi-guo Xue; Jiang Zhao; Fan-meng Kong; Sheng-yong Dong; Gang Li; Xin-shun Li; Ao-xiong Shu; Hao-ran Zhu (Applied Geophysics, 2026)

Eucommia ulmoides leaf extract enhanced growth, supported liver and intestinal function, modulated gut microbiota composition, and increased disease resistance in juvenile largemouth bass (Micropterus salmoides) - Qiang Hao; Tsegay Teame; Rui Xia; Qianwen Ding; Yuanyuan Yao; Chao Ran; Yalin Yang; Zhen Zhang; Zhigang Zhou (Aquaculture, 2026)

Integrated transcriptomic and physiological analysis highlights the candidate genes regulating enzymatic browning, antioxidant capacity, and lipid metabolism in pomegranate aril browning - Yawen Shen; Sen Wang; Ran Wan; Jian Jiao; Yujie Zhao; Liu Cong; Kunxi Zhang; Pengbo Hao; Yu Liu; Wanyu Xu; Miaomiao Wang; Jiangli Shi; et al. (Postharvest Biology and Technology, 2026)

The gut as a reservoir of drug-resistant pathogens: Mechanisms of ENR-driven horizontal gene transfer in aquaculture - Bian-Hao Zeng; Ping Li; Hao-Ran Zhang; Bang-Hua Xia; Bin Liu; Ling-Ming Kong; Ling Liu; Zhi-Hua Li (Journal of Hazardous Materials, 2026)

Towards zero liquid discharge: Resource recovery and circular economy pathways via bipolar membrane electrodialysis - Hao-Ran Yang; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Ying Chen; Yuan Liu (Chemical Engineering Journal, 2026)

Sulfonated polyarylene ether nitrile membranes impregnated with silver nanoparticles for enhanced dye/salt separation - Qimeng Ran; Chenyi Xiong; Junni Xie; Libo Hao; Xingbao Yang; Xiaohong He; Dawei Zhang; Dongsheng Wang; Xiaobo Liu; Kun Jia (Chemical Engineering Journal, 2026)

Flexible-rigid coupling configuration for advanced energy-sensing integrated microsystems - Chang-Liu He; Yao Tan; Hao Zheng; Cheng Tu; Xin-Ran Zhang; Dong-Ming Fang; Xu Zeng; Xiao-Sheng Zhang (Chemical Engineering Journal, 2026)

Effects of chronic social defeat stress on behavior and cognition by activating the ERS-NLRP3 signaling pathway in adult mice - XiaoLei Gao; Ran Hao; ZengYun Jing; GuangBiao Huang; Lina Wang; Anna Ma; ZhaoHui Zhang; Tong Zhao (Metabolic Brain Disease, 2025)

The coexistence of Bacillus haynesii and Bacillus tequilensis achieves synchronous algicidal activity and denitrification and enhances the MC-LR degradation of phycosphere microbiota - Yuzi Xing; Lei Zheng; Zixuan Li; Guizhen Hao; Xue Wang; Ran Tao; Qi Tian; Yaoxin Zhang; Haozhe Zhang (Journal of Hazardous Materials, 2025)

Liquid-like PDMS brushes/TiO2 microcapsule-driven coatings with integrated self-healing, photodegradation, and antifouling functions - Jingjing Ren; Taolin Zhang; Shouzheng Jiao; Fanghua Pan; Jingru Sun; Ran Mo; Yuwei Hao; Zhengyu Chen; Siqiao Zhang; Zhicheng Sun; Zhongjun Cheng (Journal of Environmental Chemical Engineering, 2025)

Optimizing housefly larval bioconversion of silkworm excrement through wheat bran Supplementation: Enhanced cellulose degradation and nutrient recovery - Chen Chen; Yuanhao Zhang; Xueming Xu; Xueping Jiang; Jieling Zhou; Jia Kong; Ran Zhang; Hao Li; Zhongzheng Gui (Journal of Asia-Pacific Entomology, 2025)

Highly selective electrocatalytic H2O2 generation catalyzed by cobalt- and nitrogen-modified molybdenum carbide in acidic electrolyte - Ran Mao; Shen Zhao; Zhen Wei; Jingwei Hao; Weiyue Dang; Haimin Zhang; Xu Zhao (Chemical Engineering Journal, 2025)

Promoting nitrogen removal in low C/N wastewater treatment by S0 packed-bed process: Post polishing or via disproportionating sulfidogenesis enhancement - Cong Fang; Guijiao Zhang; Wenwei Liao; Ran Zeng; Na Zhang; Bin Gao; Jiamin Xu; Chengyan Liu; Aijie Wang; Hao-Yi Cheng (Chemical Engineering Journal, 2025)

Superior degradation of endocrine disruptors over defective iron pyrites assisted by vacancy-induced disassociation of hydrogen peroxide - Han-Liang Fang; Yu-Hang Xu; Xiang-Min Jin; Hao-Ran Long; Wen-Ni Zhang; Han-Hui You; Zhou Zhong; Yi-Dong Hou; Hai-Lei Cao; Christopher Rensing; Jian Lü (Chemical Engineering Journal, 2025)

Flexible solar evaporator for simultaneous desalination and VOCs removal from seawater - Long-Feng Hu; Huiting Zhang; Huan Lin; Hui Niu; Hao-Ran Chen; Quan-Fu An (Chemical Engineering Journal, 2025)

Machine Learning Improves Mesoscale Offshore Wind Resource Assessment over the Yellow Sea - Haixing Gong; Kan Yi; Dinghua Yang; Wenyu Huang; Chenqing Fan; Ran Hao; Lina Sha; Mengke Deng; Hao Zhang (Journal of Meteorological Research, 2025)

Application of a deep learning model with physical model constraints and attention mechanism for state prediction in high-power power-shift tractors - Li-quan Lu; Ze-peng Zhang; Guang-lin Zhang; Bing Han; Hao-ran Yang; Zhong-xiang Zhu; Zheng-he Song; Zhi-qiang Zhai; Jian-hua Wang; Chuan-chuan Zhang (Computers and Electronics in Agriculture, 2025)

Bifidobacterium animalis subsp. Lactis A6 alleviates comorbid constipation and depression by rebalancing tryptophan metabolism - Jian Wang; Yimei Ren; Juan Chen; Shanbin Chen; Xiaoxia Li; Jianwen Chen; Xifan Wang; Lijun Li; Liang Zhao; Yixuan Li; Qi Zhang; Wei Xiong; et al. (Science Bulletin, 2025)

Regulation of phytoplankton community by mesoscale eddies and the East Indian Coastal Current in the southwestern Bay of Bengal during the northeast monsoon - Hao Chen; Yuanli Zhu; Lihua Ran; Mengjia Zhang; Xiao Ma; Hongliang Li; Feng Zhou; W.N.C. Priyadarshani; Zhibing Jiang (Marine Environmental Research, 2025)

Machine learning decoding of electronic thresholds in prediction of oriented generation of solar-induced oxidative reactive species and antibiotics degradation - Hao Bi; Zhiruo Zhou; Qian Liu; Ran Zhao; Fangyuan Chen; Jun Zhang; Zhurui Shen (Journal of Hazardous Materials, 2025)

A highly fractionated origin for the Yanshanian water-rich A-type granite in the Southern Great Xing’an Range, NE China: Insights from zircon and monazite geochemistry - Zi-Yi Wang; Hao Yang; Hao-Ran Wu; Zhi-Chao Zhang; Zheng Ji; Yu Dong; Wen-Chun Ge (Journal of Asian Earth Sciences, 2025)

Post-heat treatment and pectin addition affect protein digestion and absorption release kinetics in pigs through microstructural and rheological modifications - Xiyu Qin; Xiuying Wu; Caiziyu Yu; Yi Chai; Xiaoxue Liu; Xiaoxu Zhang; Huifang Cai; Mengxuan Lai; Lili Qiu; Yanling Hao; Ran Wang; Yixuan Li; et al. (Food Chemistry, 2025)

Heat treatment affects gastric digestion kinetics but not amino acid bioavailability of milk proteins: a pig study - Xiyu Qin; Caiziyu Yu; Xiaolu Geng; Yi Chai; Xiaoxue Liu; Xiaoxu Zhang; Menghui Wang; Xiaomin Ren; Yanling Hao; Ran Wang; Yixuan Li; Pengjie Wang; et al. (Food Chemistry, 2025)

Unraveling mulberry anthocyanins’ antioxidant mechanism and biosafety via computational modeling - Jianglong He; Yuqi Li; Xueping Jiang; Haoran Huang; Yue Zhang; Ran Zhang; Hao Li; Zhongzheng Gui (Food Bioscience, 2025)

SERS detection of lung cancer-related volatiles in exhaled breath utilizing size controllable Au NC@ZIF-8 core-shell nanoparticles - Zixuan Wang; Wei Ran; Juan Shen; Yuanyuan Cao; Zhongzhong Wang; Simeng Zhang; Rongzhang Hao (Chemical Engineering Journal, 2025)

From growth to decline: The dynamic effects of maize-based cropping systems on soil organic carbon storage in Northeast China - Jin-Sai Chen; Zhuo Shi; Yu-Gang Tian; Hao-Ran Li; Hong-Xuan Duan; Zhi-Heng Qin; Jia Cheng; Yash Pal Dang; Bai-Jian Lin; Xin Zhao; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2025)

Comparative Genomics Uncovers Molecular Adaptations for Cetacean Deep‐Sea Diving - Fan Zhang; Tong Zhang; Hao Dong; Jie Jiang; Guang Yang; Inge Seim; Ran Tian (Molecular Ecology, 2025)
Cetaceans show remarkable diversity in diving capability, implying a range of adaptive strategies to hazards such as hydrostatic pressure and oxidative stress, but few studies have considered the evolution of extreme diving. Here, we first examined the relationship between morphological and physiological factors and diving capability and then considered the molecular evolution of candidate deep‐sea diving traits in a genomic dataset of cetaceans. Our dataset included six super‐divers, sperm whales (families Physeteridae and Kogiidae) and beaked whales (Ziphiidae), species that can dive deeper than 1000 m for about an hour or longer. We found a positive association between diving capability and oxygen‐linked globins, and super‐diver myoglobin ( MB ) is under positive selection and harbours a reported functional amino acid change. Blubber thickness was positively associated, likely to provide thermal insulation and hydrostatic pressure resistance. Super‐divers have gene changes that may contribute to differences in the composition of outer blubber neutral lipids (triacylglycerols and wax esters), fatty acids and cholesterol. Total lung capacity relative to body mass showed a negative association, ostensibly to limit gas bubbles that can cause decompression sickness. A functional assay suggests that an ATP8B1 amino acid substitution may reduce lung injury in super‐divers. Super‐diver XDH has two unique amino acids and a decreased ability to produce uric acid under hypoxia when its ROS‐generating XO isoform is prevalent, suggesting that it reduces cell damage from oxidative stress and uric acid accumulation in species with prolonged dives. Our study deepens the understanding of how deep‐sea diving emerged in the cetacean lineage.

Aridity Drives the Response of Soil Organic Carbon and Inorganic Carbon to Drought in Cropland - Shou‐Wei Han; Qing Luo; Zhi‐Heng Qin; Wen‐Sheng Liu; Hao‐Ran Li; Rattan Lal; Yash Pal Dang; Pete Smith; Xin Zhao; Hai‐Lin Zhang (Global Change Biology, 2025)
In the face of a warming climate and increasing extreme weather events, understanding the trade‐offs between soil organic carbon (SOC) and inorganic carbon (SIC) under drought is critical for accurately assessing global soil carbon (C) sequestration. However, previous research has predominantly focused on SOC, despite emerging evidence indicating that SIC is highly sensitive to soil moisture dynamics. Using global soil profile C measurements, this study compares the relative ratio of SOC and SIC to soil total carbon (STC) in cropland to assess the impact of climatic drought on soil C pools. The research findings revealed that STC stocks averaged 8.0, 16.7, and 21.6 kg C m −2 at soil depths of 0–30 cm, 30–100 cm, and 100–200 cm, respectively. The STC in the deep soil depths (100–200 cm) responded linearly to the drought gradient, whereas STC in the surface layer showed a nonlinear response. It is notable that the ratio of SIC to STC increased along the drought gradient. Irrigation, a key drought mitigation strategy, increased the ratio of SIC in dry sub‐humid regions but reduced it elsewhere. These findings highlight the importance of incorporating SIC into climate change mitigation strategies, especially in the context of intensifying drought conditions.

In-situ formation of green rust during Fe(II) coagulation: Dual reductive and adsorptive pathways for dyeing wastewater treatment - Xian Zhao; Jia-Yi Wang; Yu-Qian Wang; Chen-Hao Cui; Xin Yan; Wei Dai; An-Ran Zhang; Zhen-Ying Zhang; Ding-Ding Tang; Yan Zhou; Qiong Qin; Ji-Wei Pang; et al. (Water Research, 2025)

A laser with instability reaching 4 × 10 - 17 based on a 10-cm-long silicon cavity at sub-5-K temperatures - Zhi-Ang Chen; Hao-Ran Zeng; Wen-Wei Wang; Han Zhang; Run-Qi Lei; Jian-Zhang Li; Cai-Yin Pang; She-Song Huang; Xibo Zhang (Science Bulletin, 2025)

The early Holocene vegetation history and quantitative reconstruction of climate in the Chahanur Lake, Inner Mongolia Plateau, China - Xu-Ran Zhang; Hua-Yong Zhang; Zhong-Yu Wang; Hao Chen; Xiao-Chang Wu; Zhao Liu (Palaeoworld, 2025)

LLTO-based electrodes for selective lithium extraction from high Mg2+/Li+ brines: Performance and mechanistic insights - Ran Zhang; Jialu Chen; Qian Xu; Beichen Sun; Xiao Du; Shanxia Luo; Xiaogang Hao (Journal of Environmental Chemical Engineering, 2025)

Operational optimisation of domestic refrigerators based on user behaviour prediction and deep reinforcement learning - Hao-Ran Li; Wei Zhang; Qiang Chen (International Journal of Refrigeration, 2025)

Chemotaxis-driven Stenotrophomonas pavanii surface-aggregated FastPETase system for in situ degradation of PET microplastics - Si-Qi Chen; Qing-Song Huang; Yang Li; Hao-Ran Zhang; Yan Huang; Jing Wu; Sheng Chen; Zheng-Fei Yan (Chemical Engineering Journal, 2025)

Contrasting impacts of grassland restoration methods on soil greenhouse gases emissions under warming conditions in Northern Tibet - Hao Shi; Fei Xia; Lin-ling Ran; Hao-yang Wu; Jun-qiang Wang; Yun-yin Xue; Wei Wei; Shai-kun Zheng; Shuang Yan; Cai-hong Yang; Yu Zhang; Xiao-qin Qiu (CATENA, 2025)

Retraction Note: Reconstructing mantle–crust boundary magmatism through Cimmerian orogenic events: evidence from deep crustal cumulates in northeastern Pamir - Masumeh Sargazi; Chuan-Lin Zhang; Yan Jing; Zahid Hussain; Zhi-Hao Song; Hong-Ran Wang; Xiao-Qiang Liu; Xian-Tao Ye (Contributions to Mineralogy and Petrology, 2025)

Flavonoids as Signals Mediate Plant-nematode Communication Through Regulating Nematode Perceptual Ability - Xiang-Yu Zhang; Rui Yuan; Yaseen Ullah; Xu-Dong Li; Hao-Ran Li; Wei Zhang (Journal of Chemical Ecology, 2025)

Grazing mediates soil nutrient stocks through changing the plant functional composition and plant biomass allocation in alpine grassland - Fengcai He; Shikui Dong; Chunhui Ma; Xinghai Hao; Hao Shen; Juejie Yang; Jiannan Xiao; Yu Li; Ran Zhang; Hang Shi; Ziying Wang; Yuhao Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

A novel dynamic membrane-equipped element sulfur-based denitrification reactor for efficient and easily maintainable treatment of high-nitrate wastewater - Na Zhang; Xiang-Li Zeng; Wen-Wei Liao; Meng-Yi Chen; Guijiao Zhang; Da-Heng Ren; Xu-Chen Ba; Min-Kun Zhang; Hao-Ran Xu; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

Ecological stoichiometry of carbon, nitrogen, phosphorus, and silicon in coastal salt marsh plants and its implications for carbon sink management - Xinyu Zhang; Zhaoliang Song; Yuntao Wu; Lele Wu; Qiang Li; Qian Hao; Shaopan Xia; Yidong Wang; Xiangbin Ran; Yunying Fang; Hailong Wang (Journal of Environmental Management, 2025)

Logic-gate nanocompiler for oxidative/reductive molecular parallel detection during hepatic ischemia-reperfusion injury - Tao Tang; Fushou Liu; Longshua Qin; Hao Li; Wen-Ping Lin; Yi-Ping Gu; Fangtao Tan; Linfeng Wang; Huan Liu; Mingxi Zhang; Ran Cui (Chemical Engineering Journal, 2025)

Probabilistic failure mode-based prediction method for flexural design capacities of precast reinforced concrete and prestressed concrete beams - Yukun Hu; Jitao Yao; Kaikai Cheng; Luyang Zhang; Meng Ran; Hao Li; Jiewei Xu (Bulletin of Earthquake Engineering, 2025)

Synergistic effects of environmental factors on benthic diversity: Machine learning analysis - Yiyang Feng; Mengyu Yang; Hao Chen; Kun Zhang; Fuju Ran; Ziyan Chen; Haijun Yang (Water Research, 2025)

Feedback inhibition derived from hydrogen sulfide in microbial sulfidogenic process via elemental sulfur disproportionation - Guijiao Zhang; Hao-Ran Xu; Wenwei Liao; Jia-Min Xu; Na Zhang; Daheng Ren; Xuchen Ba; Wenyan Mao; Wenke He; Cong Fang; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

Strain-specific effects of fish originated Bacillus velezensis on growth, gut health, and disease resistance of zebrafish - Yuan-Yuan Yao; Wen-Hao Zhou; Juan Hu; Ya-Lin Yang; Ming Li; Rui Xia; Chao Ran; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2025)

Effect of cadmium-resistant Proteus mirabilis Ch8 on active ingredients and cadmium content of traditional Chinese medicine Ligusticum sinense cv. Chuanxiong - Ting Li; Lin Liu; Xiu-wen Bao; Fei-fei Liu; Xuan Zhang; Hao-ran Song; Si-jing Liu; Jing Bai; Qing-he Wang; Fei-lin Yang; Yang Li; Shu-qi Niu; et al. (Plant and Soil, 2025)

Effects of nitrogen deposition on temporal stability and resistance of the alpine steppe plant communities on the Qinghai-Tibetan Plateau - Ran Zhang; Hao Shen; Shikui Dong; Qiang Yu; Bing Zhang; Jiannan Xiao; Shuai Li; Hui Zuo; Hang Shi; Fengcai He; Ke Zhang; Yuhao Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Rotational grazing can enhance the soil available nutrients rather than plant diversity to promote ANPP of alpine steppe - Fengcai He; Shikui Dong; Juejie Yang; Xinghai Hao; Chunhui Ma; Hao Shen; Jiannan Xiao; Yu Li; Ran Zhang; Hang Shi; Ziying Wang; Yuhao Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Transcriptome Analysis Reveals Hyperglycemic Hormone and Excitatory Amino Acid Transporter 3 Are Involved in the Thermal Adaptation of Eriocheir sinensis - Xi Li; Runlin Zhou; Ruiqi Zhang; Zhen He; Mingzhi Zhang; Ran Li; Tong Hao; Jinsheng Sun (Fishes, 2025)
Temperature is one of the critical factors influencing the survival, growth, and reproduction of organisms. The molting and developmental mechanisms of crustaceans are highly sensitive to temperature, yet the regulatory mechanisms underlying their thermal adaptation remain unclear. In this work, transcriptome sequencing was performed to analyze the gene expression profiles of Eriocheir sinensis under normal temperature (22 °C) and high-temperature (27 °C and 32 °C) conditions. A total of 377 differentially expressed genes (DEGs) were identified, including 149 up-regulated and 227 down-regulated genes. Through Gene Ontology (GO) enrichment analysis of these DEGs, 11 significantly temperature-regulated signaling pathways were identified, including the estrogen and androgen receptor signaling pathways, and two neurotransmission signaling pathways. These findings suggest that temperature may influence sex regulation in E. sinensis, while the dopamine receptor and neuropeptide signaling pathways may play a role in its thermal adaptation. Further validation via RT-qPCR of DEGs involved in neurotransmission signaling pathways revealed that crustacean hyperglycemic hormone (CHH) and excitatory amino acid transporter 3 (EAA3) genes are likely involved in the thermal adaptation of E. sinensis. In addition, the hemolymph glucose levels associated with the elevated temperatures were detected and consistent variations between glucose levels and CHH expressions were found. This indicates that the eyestalk CHH is strongly correlated with the hemolymph glucose levels and likely mediates the response to temperature changes by regulating blood glucose in E. sinensis. The results of this study not only provide key molecular targets for elucidating the mechanisms by which temperature affects molting and development in E. sinensis, but also establish a theoretical foundation for further research into thermal adaptation strategies in crustaceans.

Synergistic coupling of bipolar membrane electrodialysis and Fenton process for sustainable management of landfill leachate reverse osmosis concentrate - Hao-Ran Yang; Changjiang Li; Chiqian Zhang; Xiaohong Lan; Xinfei Dong; Yi-Hong Jiang; Yu-Ming Zheng; Zhi-Hua Yuan (Chemical Engineering Journal, 2025)

A versatile and double cross-linked hydrogel with potent antibacterial and immunomodulatory Zn@Met nanocomplexes for enhanced diabetic-infected wound healing - Tinglong Chen; Xueliang Zhang; Shengzhe Zhou; Dong Fang; Dinghao Luo; Zhaoyang Ran; Yingchun Liu; Cheng Xu; Jinhao Cao; Xiaodong Li; Yongqiaong Hao; Xiaoqing Wang; et al. (Chemical Engineering Journal, 2025)

Genomic and transcriptomic insights into the cellulose-degrading mechanism of Bacillus subtilis DC-11 and its novel cellulose catabolic pathway - Chen Chen; Minqi Zhang; Yuanhao Zhang; Xueping Jiang; Jia Kong; Jieling Zhou; Gaiqun Huang; Ran Zhang; Hao Li; Zhongzheng Gui (Archives of Microbiology, 2025)

Near-complete recovery of phosphorus from fresh human urine: Combining magnesium-air fuel cells with modified granular attapulgite - Lin-Jiang Zhong; Lin-Feng He; Hao-Ran Yang; Shu-Jie Hu; Di Wu; Meng-Yue Zhang; Ying Chen; Xuan Zhao; Hong Liu; Yuan Liu (Journal of Environmental Management, 2025)

A novel ciprofloxacin-degrading bacteria Phytobacter diazotrophicus SMX isolated from silkworm faeces: characteristics, degradation metabolites, and toxicity assessment - Jia Kong; Xueping Jiang; Yuqi Li; Jielin Zhou; Ran Zhang; Hao Li; Zhongzheng Gui (Journal of Asia-Pacific Entomology, 2025)

Short-term P addition weakens the positive effects of N addition on CH4 uptake in alpine grasslands of the Qinghai-Tibetan Plateau - Jiannan Xiao; Shikui Dong; Hao Shen; Ran Zhang; Hang Shi; Fencai He; Wei Li; Xiaoyan Li (Plant and Soil, 2025)

The growth performance in different seasons of Homatula variegata (Dabry de Thiersant, 1874) in Northern Guizhou, China - Gui Bang Xiao; Qi Wei Guo; Wei Xi Deng; Qi Qi Xiao; Lin Zhou; Hao Ran Zhang; Jia Lin; Ding Zhi Fang (Journal of Comparative Physiology B, 2025)

Virtual screening and characterization of novel myogenic peptides from bovine collagen hydrolysates: Targeting myomaker - Hanfeng Li; Yunci Wang; Xiao Yong Ran; Qi Hao; Jianing Wang; Bing Zhang; Yanchuan Guo (Food Research International, 2025)

The simulated in vitro infant gastrointestinal digestion of lipid droplets covered with milk fat globule membrane components: The role of interface layers - Zhixi Li; Yu Cao; Xiankang Fan; Hui Zhou; Pengjie Wang; Hao Zhang; Yi Wang; Ran Wang; Jie Luo (Food Research International, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

Endophytic fungi promote peanut fitness by re-establishing rhizosphere nematode communities under continuous monocropping conditions - Xiang-Yu Zhang; Hao-Ran Li; Hui-Jun Jiang; Xiao-Han Wu; Chen-Yu Ma; De-Lin Luo; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

The role and function mechanism of pilV in modulating the pathogenicity of Aeromonas hydrophila - Zhengshi Zhang; Jiayan Ran; Shengfu Zhao; Hui Luo; Shuqing Zheng; Detao Li; Ziyang Li; Yongyao Yu; Hao Xu; Ronghua Wu; Hua Ye (Aquaculture, 2025)

Indian ocean-type mantle domain in the Carboniferous Qushiman ophiolite in the Northern Pamir: Significance for the intra-oceanic subduction in the Paleo-Tethys Ocean - Yan Jing; Chuan-Lin Zhang; Chen Wang; Masumeh Sargazi; Zhi-Hao Song; Yi-kang Quan; Zhi-Kai Xu; Xiao-Qiang Liu; Hong-Ran Wang (Chemical Geology, 2025)

Bed-immersion-ratio variation as an efficient strategy to regulate denitrification efficiency directionally in elemental sulfur packed-bed reactors - Guijiao Zhang; Hao-Ran Xu; Wenwei Liao; Jia-Min Xu; Na Zhang; Daheng Ren; Xinjie Chen; Wenyan Mao; Xiangli Zeng; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Tillage effects on maize yield, N use efficiency and GHG emissions under parallel N application in Northwest China - Hao-yang Wu; Lin-ling Ran; Jun-qiang Wang; Shuang Yan; Yun-yin Xue; Fei Xia; Hao Shi; Wei Wei; Yu Zhang; Shai-kun Zheng (Field Crops Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Cellular mechanism of polarized auxin transport on fruit shape determination revealed by time-lapse live imaging - Yao Zhang; Hao-Ran Sun; Zhi-Cheng Hu; Yang Dong (Plant Reproduction, 2025)

Transcriptome analysis reveals the dynamics of gene expression during early embryonic development of hybrid groupers - Fengying Yan; Chongwei Wang; Yuzhi Zhu; Jinhui Wu; JiayuYang; Songyong Gan; Hao Ran Lin; Yong Zhang; Shuisheng Li (Aquaculture, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Central core regulation by methoxy in quinoxaline-based non-fullerene acceptors for over 19 % efficiency organic solar cells - Huijuan Bi; Dingding Qiu; Hao Zhang; Caixuan Wang; Mengying Wu; Xinya Ran; Jianqi Zhang; Yuheng Wang; Ailing Tang; Xinyang Miao; Zhixiang Wei; Kun Lu (Chemical Engineering Journal, 2025)

RETRACTED ARTICLE: Reconstructing mantle–crust boundary magmatism through Cimmerian orogenic events: evidence from deep crustal cumulates in northeastern Pamir - Masumeh Sargazi; Chuan-Lin Zhang; Yan Jing; Zahid Hussain; Zhi-Hao Song; Hong-Ran Wang; Xiao-Qiang Liu; Xian-Tao Ye (Contributions to Mineralogy and Petrology, 2025)

Comprehensive analysis of biotransformation pathways and products of chloramphenicol by Raoultella Ornithinolytica CT3: Pathway elucidation and toxicity assessment - Xueping Jiang; Hao Li; Jia Kong; Yuqi li; Xiangdong Xin; Jielin Zhou; Ran Zhang; Kwang Sik Lee; Byung Rae Jin; Zhongzheng Gui (Journal of Hazardous Materials, 2024)

Alterations in the nutrient composition, muscle quality, and proteomics of two Sepiidae species (Sepiella maindroni and Sepia esculenta) during storage - Shan-Shan Jiang; Hao-Ran Lv; Hui-Min Lin; Jie Feng; Soottawat Benjakul; Shucheng Liu; Bin Zhang (Food Bioscience, 2024)

Peroxymonosulfate-based electrochemical advanced oxidation for pollutant degradation: Roles of Co-phase regulation and electro-induced polarized particle electrodes - Yunlong Liu; Ran Hao; Zhenyu Shi; Wei Zhang; Can Jin; Liang Zhu; Chunmei Tang; Guifeng Liu; Shuping Huo; Lin Xu; Zhenwu Kong (Chemical Engineering Journal, 2024)

Different responses of individuals, functional groups and plant communities in CSR strategies to nitrogen deposition in high-altitude grasslands - Xueqi Li; Ying Li; Hao Shen; Shuai Li; Zhenzhen Zhao; Jiannan Xiao; Ran Zhang; Hang Shi; Hui Zuo; Tu Danjia; Guoming Chen; Xueli Zhou; et al. (Science of The Total Environment, 2024)

MdAP2-like, a new regulator in apple, simultaneously modulates fruit softening and size - Miaomiao Wang; Wenduo Zhan; Ming Chen; Yanfei Guo; Hao Wang; Yao Wu; Tuanhui Bai; Jian Jiao; Chunhui Song; Jiangli Shi; Ran Wan; Kunxi Zhang; et al. (Postharvest Biology and Technology, 2024)

Effects of 1-oleate-2-palmitate-3-linoleate glycerol supplementation on the small intestinal development and gut microbial composition of neonatal mice - Fang Wu; Yaqiong Liu; Ming Zhang; Xinlei Yuan; Tengteng Ji; Yutong Jin; Yixuan Li; Ran Wang; Yanling Hao; Bing Fang (Food Research International, 2024)

Greenhouse gas emissions and mitigation potential of crop production in Northeast China - Jin-Sai Chen; Hao-Ran Li; Yu-Gang Tian; Ping-Ping Deng; Olatunde Pelumi Oladele; Wei Bai; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (European Journal of Agronomy, 2024)

Delaying cyclization of polyacrylonitrile by boric acid for sulfurized poly(acrylonitrile) cathode materials - Xuan Zhang; Hui-Chao Lu; Chen-Ran Hao; Ji-Qiong Liu; Xi-Rui Kong; Jiu-Lin Wang (Chemical Engineering Journal, 2024)

Reconciled estimation of Antarctic ice sheet mass balance and contribution to global sea level change from 1996 to 2021 - Rongxing Li; Guojun Li; Gang Hai; Huan Xie; Yuan Cheng; Wei Chen; Xiangbin Cui; Minghu Ding; Chunchun Gao; Tong Hao; Changqing Ke; Chuanjin Li; et al. (Science China Earth Sciences, 2024)
The Antarctic Ice Sheet (AIS) has been losing ice mass and contributing to global sea level rise (GSLR). Given its mass that is enough to cause ∼58 m of GSLR, accurate estimation of mass balance trend is critical for AIS mass loss monitoring and sea level rise forecasting. Here, we present an improved approach to reconciled solutions of mass balance in AIS and its regions from multiple contributing solutions using the input-out, altimetric, and gravimetric methods. In comparison to previous methods, such as IMBIE 2018, this approach utilizes an adaptive data aggregation window to handle the heterogeneity of the contributing solutions, including the number of solutions, temporal distributions, uncertainties, and estimation techniques. We improved the regression-based method by using a two-step procedure that establishes ensembled solutions within each method (input-output, altimetry, or gravimetry) and then estimates the method-independent reconciled solutions. For the first time, 16 contributing solutions from 8 Chinese institutions are used to estimate the reconciled mass balance of AIS and its regions from 1996 to 2021. Our results show that AIS has lost a total ice mass of ∼3213±253 Gt during the period, an equivalent of ∼8.9±0.7 mm of GSLR. There is a sustained mass loss acceleration since 2006, from 88.1±3.6 Gt yr −1 during 1996–2005 to 130.7±8.4 Gt yr −1 during 2006–2013 and further to 157.0±9.0 Gt yr −1 during 2014–2021. The mass loss signal in the West Antarctica and Antarctic Peninsula is dominant and clearly presented in the reconciled estimation and contributing solutions, regardless of estimation methods used and fluctuation of surface mass balance. Uncertainty and challenges remain in mass balance estimation in East Antarctica. This reconciled estimation approach can be extended and applied for improved mass balance estimation in the Greenland Ice Sheet and mountain glacier regions.

Concentration and activation biresponsive strategy in one analysis system with simultaneous use of G4 structure-specific signal probe and enzyme-catalyzed reaction - Yu-Shu Li; Chun-Feng Feng; Hao-Ran Chen; Wei-Guo Yang; Fei Liu; Ming-Li Su; Ruo Yuan; Li-Qun Zhang; Wen-Bin Liang (Analytica Chimica Acta, 2024)

Advanced electrochemical membrane technologies for near-complete resource recovery and zero-discharge of urine: Performance optimization and evaluation - Hao-Ran Yang; Yuan Liu; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Chuan Wang; Hong Liu (Water Research, 2024)

Freshwater microconchids from the Tanzhuang Formation (Middle-Late Triassic) in North China - Hao Yang; Yue Su; Hui-Jun Chen; Yi-Ran Cao; Meng-Yang Zhang; Rui Li; Dao-Liang Chu (Palaeoworld, 2024)

Characteristics of corn starch/polyvinyl alcohol composite film with improved flexibility and UV shielding ability by novel approach combining chemical cross-linking and physical blending - Hao-Nan Wei; Xin-Yue Liu; Chen-Chen Wang; Ran Feng; Bao Zhang (Food Chemistry, 2024)

Combining GC–MS/MS with a LLE-SPE sample pretreatment step to simultaneously analyse enrofloxacin and ofloxacin residues in chicken tissues and pork - Maoda Pang; Junjie Xu; Yayun Tang; Yawen Guo; Hao Ding; Ran Wang; Tao Zhang; Genxi Zhang; Xiaodong Guo; Guojun Dai; Xing Xie; Kaizhou Xie (Food Chemistry, 2024)

Distribution characteristics of sulfonamide antibiotics between water and extracellular polymeric substances in municipal sludge - Ming Cheng; Chen Shi; Bo-Han Zhao; Tai-Yue Wang; Nan-Zhang; Ran-Bin Liu; Da-Qi Cao; Xiao-Di Hao (Environmental Research, 2024)

Silicon promotes biomass accumulation in Phragmites australis under waterlogged conditions in coastal wetland - Yuntao Wu; Xiaodong Zhang; Jiayang Lin; Xia Wang; Shaobo Sun; Qian Hao; Lele Wu; Jingyun Zhou; Shaopan Xia; Xiangbing Ran; Yidong Wang; Jiahuan Tang; et al. (Plant and Soil, 2024)

Whole Genome Sequencing Analysis of Cellulose-degrading Bacterium DC11 Isolated from Silkworm Excrement and Characterization of Its Key Cellulase Gene ytoP - Yuanhao Zhang; Hao Li; Minqi Zhang; Xueping Jiang; Chen Chen; Xiaohui Zhang; Ran Zhang; Gaiqun Huang; Gang Liu; Zhongzheng Gui (Journal of Asia-Pacific Entomology, 2024)

Electrolyte matching design for carboxylic acid-based organic K-storage anode - Jing Zheng; Hao Wang; Chi Hu; Hang Chen; Wanying Zhang; Xiaokang Chu; Luanjie Nie; Ran Chen; Jianying Long; Meng Lei; Jijian Xu; Zixia Lin; et al. (Chemical Engineering Journal, 2024)

Water flush boosts performance of elemental sulfur-based denitrification packed-bed systems: Optimization and mechanisms - Jia-Min Xu; Heng Dong; Hao-Ran Xu; Yi-Lu Sun; Yang Yu; Li-Ying Zhang; Gen-Ping Yi; Wen-Ke He; Chang-Min Wu; Ai-Jie Wang; Hao-Yi Cheng (Bioresource Technology, 2024)

Jianpi Huayu Prescription Prevents Atherosclerosis by Improving Inflammation and Reshaping the Intestinal Microbiota in ApoE−/− Mice - Hao-Ran Zhao; Qin-Chi Xian; Xuan-Ming Zhang; Xiao-Yu Ma; Fu-Qiao Wang; Rui-Si Wang; Zhi-Jie Liu; Zhi-Gang Zhang (Cell Biochemistry and Biophysics, 2024)
This study established an LPS-induced RAW264.7 macrophage inflammatory injury model and an AS mouse vulnerable plaque model to observe the effect of JPHYP on macrophage inflammation, plaque formation, blood lipids, inflammation levels, intestinal flora and the influence of TLR4/MyD88/MAPK pathway, and explore the anti-AS effect and molecular mechanism of JPHYP, and detected 16S rRNA of mice intestinal microbes. The difference of intestinal flora in different groups of mice was compared to further explore the intervention effect of JPHYP and clarify the molecular biological mechanism of JPHYP in preventing and treating AS by regulating TLR4/MyD88/MAPK inflammatory signaling pathway and improving intestinal flora.

Studies on 1-deoxynojirimycin biosynthesis in mulberry ( Morus alba L.) seeds through comparative transcriptomics - Xiangdong Xin; Xueping Jiang; Attaribo Thomas; Baoxin Niu; Minqi Zhang; Xueming Xu; Ran Zhang; Hao Li; Zhongzheng Gui (Natural Product Research, 2024)

Geochronology and Sr-Nd-Pb-Hf-O isotopes of Neoproterozoic orthogneisses in the Jiamusi Block, NE China: Implications for tectonic origin and secular crustal evolution - Xin Ding; Hao Yang; Zheng Ji; Yan-Long Zhang; Hao-Ran Wu; Yu Dong; Guan-Ying Yu; Wen-Chun Ge (Precambrian Research, 2024)

Fish decay-accelerating factor (DAF) regulates intestinal complement pathway and immune response to bacterial challenge - Xia Zhang; Yuhan Zhang; Ting Wu; Hao He; Ran Peng; Kelan Jin; Huilan Mo; Fufa Qu; Jianzhou Tang; Yonghua Zhou; Yalin Yang; Zhigang Zhou; et al. (Fish & Shellfish Immunology, 2024)

Immobilization of Nickel- and Cobalt-Based Complexes in NH2-UiO-66 for Efficient CO2 Photoreduction - Yu Jiang; Si-Chao Liu; Li-Ping Zhang; Guo-Wei Guan; Yi-Tao Li; Shuang Ni; Run-Yuan Jiang; Su-Tao Zheng; Hao-Ran Liu; Hao-Ling Lan; Qing-Yuan Yang (Chemical Engineering Journal, 2024)

Involvement of CgHSFB1 in the regulation of self-incompatibility in ‘Shatian’ pummelo - Chenchen Liu; Xin Zheng; Jianbing Hu; Qiang Xu; Hao Wen; Zhezhong Zhang; Ran Liu; Xiangling Chen; Zongzhou Xie; Junli Ye; Xiuxin Deng; Lijun Chai (Plant Molecular Biology, 2024)

Effects of Tetraselmis subcordiformis (Wille) Butcher with antimicrobial peptides as feed additives on gut microbial community and immunity of turbot (Scophthalmus maximus L.) - Bingkui Zhu; Fengjie Sun; Zhengquan Gao; Ting Yao; Subing Han; Hao Zhang; Yuyang Ma; Yuyong Wu; Ran Du; Chunxiao Meng; Yulin Cui (Journal of Applied Phycology, 2024)

ML-Net: A Multi-Local Perception Network for Healthy and Bleached Coral Image Classification - Sai Wang; Nan-Lin Chen; Yong-Duo Song; Tuan-Tuan Wang; Jing Wen; Tuan-Qi Guo; Hong-Jin Zhang; Ling Mo; Hao-Ran Ma; Lei Xiang (Journal of Marine Science and Engineering, 2024)
Healthy coral reefs provide diverse habitats for marine life, playing a crucial role in marine ecosystems. Coral health is under threat due to global climate change, ocean pollution, and other environmental stressors, leading to coral bleaching. Coral bleaching disrupts the symbiotic relationship between corals and algae, ultimately impacting the entire marine ecosystem. Processing complex underwater images manually is time-consuming and burdensome for marine experts. To rapidly locate and monitor coral health, deep neural networks are employed for identifying coral categories, which can facilitate the automated processing of extensive underwater imaging data. However, these classification networks may overlook critical classification criteria like color and texture. This paper proposes a multi-local perception network (ML-Net) for image classification of healthy and bleached corals. ML-Net focuses on local features of coral targets, leveraging valuable information for image classification. Specifically, the proposed multi-branch local adaptive block extracts image details through parallel convolution kernels. Then, the proposed multi-scale local fusion block integrates features of different scales vertically, enhancing the detailed information within the deep network. Residual structures in the shallow network transmit local information with more texture and color to the deep network. Both horizontal and vertical multi-scale fusion blocks in deep networks are used to capture and retain local details. We evaluated ML-Net using six evaluation metrics on the Bleached and Unbleached Corals Classification dataset. In particular, ML-Net achieves an ACC result of 86.35, which is 4.36 higher than ResNet and 8.5 higher than ConvNext. Experimental results demonstrate the effectiveness of the proposed modules for coral classification in underwater environments.

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

A self-assembled 3D nanoflowers based nano-ELISA platform for the sensitive detection of pyridaben - He Chen; Li An; Meng Li; Hao Liu; Zhong Jin; Huan Ma; Jingwei Ma; Juan Zhou; Ran Duan; Di Zhang; Xiu Cao; Tieliang Wang; et al. (Food Chemistry, 2024)

Effect of recycled polypropylene on migration of six processing aids in polypropylene film to milk - Yi-Qi Liu; Ze-Kun Li; Hao-Ran Zhang; Zhi-Wei Wang; Chang-Ying Hu (Food Packaging and Shelf Life, 2024)

Tissue-specific responses and interactive characteristics of crop-microbe "One Health" system to soil chromium and ofloxacin pollution - Jia-Min Xu; Yaru Zhang; Kai Wang; Guodong Zhang; Ying Liu; Hao-Ran Xu; Hu-Yi Zi; Ai-Jie Wang; Yao Lv; Kun Xu; Hao-Yi Cheng (Process Safety and Environmental Protection, 2024)

Research on deep learning-based point cloud semantic segmentation for offshore drilling platforms - Hao Yu; Xiaobo Zhang; Luotao Zhang; Chunqing Ran (Ocean Engineering, 2024)

Promoting effect of polyoxometallic acid modification on the NH3-SCR performance of Mn-based catalysts - Yi Dong; Mingchu Ran; Xiao Zhang; Saisai Lin; Weixian Li; Yang Yang; Hao Song; Weihong Wu; Shaojun Liu; Chenghang Zheng; Xiang Gao (Journal of Environmental Chemical Engineering, 2024)

Discovery of abundant shock-induced metallic lead nanograins in lunar zirconolite - Ai-Cheng Zhang; Hao-Xuan Sun; Tian-Ran Trina Du; Jia-Ni Chen; Li-Xin Gu (Geochimica et Cosmochimica Acta, 2024)

Soot particles formed by n-heptane and n-heptane/oxymethylene ether-3 in an inverse diffusion flame: A comparative analysis of chemical features - Ye Liu; Ran Zhang; Jun Wang; Yajun Wang; Gang Lv; He Yang; Haibo Chen; Tiezhu Li; Bin Hao; Junhua Guo (Fuel, 2024)

Dietary Bacillus velezensis T23 fermented products supplementation improves growth, hepatopancreas and intestine health of Litopenaeus vannamei - Hongwei Yang; Dongdong Du; Qingshuang Zhang; Tsegay Teame; Anran Wang; Qiang Hao; Shubin Liu; Qianwen Ding; Yuanyuan Yao; Yalin Yang; Chao Ran; Shengkang Li; et al. (Fish & Shellfish Immunology, 2024)

Gas-to-particle partitioning of atmospheric water-soluble organic aerosols: Indications from high-resolution observations of stable carbon isotope - Hao-Ran Yu; Yan-Lin Zhang; Fang Cao; Xiao-Ying Yang; Tian Xie; Yu-Xian Zhang; Yongwen Xue (Atmospheric Environment, 2024)

Three episodes of Triassic volcanism in the Eastern Kunlun Orogen, NW China: constraints for evolution of the Palaeo-Tethys Ocean - Hao-Ran Li; Jian-Feng Qiao; Feng-Yue Sun; Ye Qian; Yan-Zhang Wang; Shahzad Bakht; Hao-Tian Liu; Yan Gu (International Geology Review, 2024)

Effects of dietary bacterial culture of fengycin-producing Bacillus subtilis on growth performance, intestinal and hepatopancreas health, intestinal microbiota and disease resistance of common carp (Cyprinus carpio) - Rui Xia; Shenghui Li; Hongwei Yang; Yajie Zhao; Tsegay Teame; Qiang Hao; Mingxu Xie; Min Li; Qile Chen; Chunling Song; Chao Ran; Yalin Yang; et al. (Aquaculture, 2024)

Improved efficiency and stability using a novel elemental sulfur-based moving-bed denitrification process - Jia-Min Xu; Hu-Yi Zi; Hao-Ran Xu; Yi-Fan Zhang; Da-Heng Ren; Ran Zeng; Gui-Jiao Zhang; Aijie Wang; Hao-Yi Cheng (Water Research, 2024)

Influence of the community assemblage on sulfur distributions in the South China sea - Hao-Quan Zhang; Juan Yu; Jing-Guang Lai; Gui-Peng Yang; Long-Fei Liu; Yu Jiang; Xin-Ran Song; Yong-Qiao Chen; Hou-Jin Zhou; Qi Zhang (Marine Environmental Research, 2024)

Promotion strategy of low-carbon multimodal transportation considering government regulation and cargo owners’ willingness - Xinghua Hu; Ruizi Cheng; Jiahao Zhao; Ran Wang; Tingting Zhang; Hao Lei; Ba Liu (Environment, Development and Sustainability, 2024)

Variations in the concentration, inventory, source, and ecological risk of polycyclic aromatic hydrocarbons in sediments of the Lake Chaohu - Hao-Ran Tian; Xi-Tao Zhang; Li-Li Zhao; Shu-Chuan Peng; Ji-Zhong Wang; Yi-Han Chen (Marine Pollution Bulletin, 2024)

First-principles design of noble metal (Rh and Pd) dispersed Janus WSTe monolayer for toxic gas sensing applications - Hao Cui; Mingxin Ran; Xiaoyan Peng; Guozhi Zhang (Journal of Environmental Chemical Engineering, 2024)

Construction of dual functional CuAl-LDHs nanocomposite loaded with IGF2BP3 siRNA for enhanced therapy of gastric cancer - Haiping Li; Yuying Zhang; Bo Huang; Feifei Yang; Qiang Ma; Xiaolin Wang; Yuying Liu; Junwu Ren; Xiaojuan Pan; Ce Liang; Shimin Wang; Hao Ning; et al. (Chemical Engineering Journal, 2024)

Insights into the response of nitrogen metabolism to sulfamethoxazole contamination in constructed wetlands with varied substrates - Ya-Ru Zhang; Jia-Min Xu; Hao-Ran Xu; Guo-Dong Zhang; Xian-Bin Liu; Hao-Yi Cheng (Bioresource Technology, 2024)

Petrogenesis of the late Cenozoic potassium-rich volcanism in the NW Tibetan Plateau: Constraints on the mantle evolution through post-orogenic events - Masumeh Sargazi; Chuan-Lin Zhang; Zhi-Hao Song; Hong-Ran Wang; Zahid Hussain; Xian-Tao Ye; Wei Wang; Xiao-Fei Du (Lithos, 2024)

Effects of nanoplastics exposure on ingestion, life history traits, and dimethyl sulfide production in rotifer Brachionus plicatilis - Juan Yu; Su Wang; Hao-Quan Zhang; Xin-Ran Song; Long-Fei Liu; Yu Jiang; Rong Chen; Qi Zhang; Yong-Qiao Chen; Hou-Jin Zhou; Gui-Peng Yang (Environmental Pollution, 2024)

Tumor microenvironment-activated hollow vanadium-based nanoplatform for precise therapy of lung cancer through synergistically reversing cisplatin resistance - Lang Ran; Jianmin Xiao; Weijie Zhang; Miaomiao Wang; Huan Xin; Huimin Li; Hong Hao; Maoyang Wang; Xiaofei Wang; Geng Tian; Guilong Zhang (Chemical Engineering Journal, 2024)

Silicon fractionations in coastal wetland sediments: Implications for biogeochemical silicon cycling - Xiangwei Zhao; Zhaoliang Song; Lukas Van Zwieten; Yidong Wang; Xiangbin Ran; Qian Hao; Juqin Zhang; Zimin Li; Jun Sun; Yuqiu Wei; Lele Wu; Shuyan Liu; et al. (Science of The Total Environment, 2024)

Effects of nitrogen application on physicochemical properties of rice starch under elevated temperature - Wenzhe Liu; Kailu Wang; Yufei Zhao; Yingying Shen; Chen Zhang; Yuxuan Peng; Xuan Ran; Hao Guo; Yanfeng Ding; She Tang (Food Chemistry, 2024)

Complexities of regulating climate by promoting marine primary production with ocean iron fertilization - Hai-Bo Jiang; David A. Hutchins; Hao-Ran Zhang; Yuan-Yuan Feng; Rui-Feng Zhang; Wei-Wei Sun; Wentao Ma; Yan Bai; Mark Wells; Ding He; Nianzhi Jiao; Yuntao Wang; et al. (Earth-Science Reviews, 2024)

Ionic liquids bonded in mesoporous HAP serve as efficient catalysts for CO2 fixation - Decun Luo; Zhen-Yu Zhang; Hao Yuan; Xi-Yang Yu; Xin Gao; Zhun Hu; Chun-Ran Chang (Chemical Engineering Journal, 2024)

A new cyclohexenone derivative from phomopsis sp. XM-01 - Cheng-Yao Wang; Dong Gan; Chen-Zhe Li; Li Zhu; Xiao-Ran Zhang; Ya-Ni Li; Xiu-Hong Wu; Hao Zhou; Le Cai (Natural Product Research, 2024)

The effects of sodium propionate on intestinal barrier function of genetically improved farmed tilapia in a high-lipid formulation - Qianwen Ding; Qiang Hao; Ya Jin; Qingshuang Zhang; Yadong Xie; Yalin Yang; Rolf Erik Olsen; Einar Ringø; Chao Ran; Zhen Zhang; Zhigang Zhou (Aquaculture, 2024)

Differences in background environment and fertilization method mediate plant response to nitrogen fertilization in alpine grasslands on the Qinghai-Tibetan Plateau - Shun He; Jianqing Du; Yanfen Wang; Lizhen Cui; Wenjing Liu; Yifan Xiao; Qinwei Ran; Linfeng Li; Zuopei Zhang; Li Tang; Ronghai Hu; Yanbin Hao; et al. (Science of The Total Environment, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Mitigating the adverse effect of warming on rice canopy and rhizosphere microbial community by nitrogen application: An approach to counteract future climate change for rice - Yingying Shen; Lei Xu; Hao Guo; Hashmi Ismail; Xuan Ran; Chen Zhang; Yuxuan Peng; Yufei Zhao; Wenzhe Liu; Yanfeng Ding; She Tang (Science of The Total Environment, 2023)

Effects of salinity on sulfur-dominated autotrophic denitrification microorganisms: Microbial community succession, key microorganisms and response mechanisms - Zhuo-Ran Li; Xue-Ning Zhang; Hong-Cheng Wang; Hao-Yi Cheng; Ai-Jie Wang; Yan-Qing Zhang; Chong-Wei Cui; Yi-Lu Sun (Chemical Engineering Journal, 2023)

Livestock grazing may weaken N deposition effects on soil C:N:P stoichiometry in alpine grassland of the Qinghai-Tibetan Plateau - Hao Shen; Shikui Dong; Shuai Li; Hanzhong Zheng; Qiyun Wang; Junxiang Liu; Jiannan Xiao; Hui Zuo; Ran Zhang; Xiuchun Yang (CATENA, 2023)

Numerical Study on Evolution Mechanism of Cut Blasting and Cavity Formation Under Confining Pressure - Hao Zhang; Tingchun Li; Xiang Gao; Qingwen Zhu; Shilin Zhang; Jinlin Ran (Rock Mechanics and Rock Engineering, 2023)

Dietary cultured supernatant mixture of Cetobacterium somerae and Lactococcus lactis improved liver and gut health, and gut microbiota homeostasis of zebrafish fed with high-fat diet - Shenghui Li; Hongwei Yang; Ya Jin; Qiang Hao; Shubin Liu; Qianwen Ding; Yuanyuan Yao; Yalin Yang; Chao Ran; Chenglong Wu; Shengkang Li; Kaimin Cheng; et al. (Fish & Shellfish Immunology, 2023)

Recovery of carbon from spent carbon cathode by alkaline and acid leaching and thermal treatment and exploration of its application in lithium-ion batteries - Hao Zhou; Dayong Zhang; Yongjun Jiang; Bo Zeng; Chenxi Zhao; Mingjie Zhang; Baiyan Zeng; Xiaoquan Zhu; Xintai Su; Valentin Romanovski; Ran Bi (Environmental Science and Pollution Research, 2023)

Two new constituents from the aerial parts of Salvia miltiorrhiza Bge - Fan Yang; Jia Li; Xin-Lei Du; Shi-Jun Wang; Xiang-Hao Xu; Yong-Qing Zhang; Ran Yang (Natural Product Research, 2023)

Mapping cropland suitability in China using optimized MaxEnt model - Xiaoliang Li; Kening Wu; Shiheng Hao; Zhang Yue; Zhao Ran; Jinliang Ma (Field Crops Research, 2023)

Evolution stage identification of haze pollution episodes in beijing using constrained dynamic time warping and multiway principal component analysis - Hao Zhang; Yilun Lin; Jinye Ran; Junyi Yu; Morui Zhu; Hengqi Li; Yongli Jiao (Environmental Modelling & Software, 2023)

Copper/gold-modified porphyrinic metal–organic frameworks nanoprobes for enhanced photodynamic/chemodynamic therapy - Jiahe Zhang; Linna Chang; Ran Hao; Gangwan Zhang; Tao Liu; Zekai Li; Tianyou Wang; Leyong Zeng (Chemical Engineering Journal, 2023)

Impact of π–bridge unit in fully nonfused ring electron acceptor on the photovoltaic performance of organic solar cells - Wenlong Liu; Xinming Zheng; Guangliu Ran; Hao Lu; Xinjun Xu; Chuang Yao; Yahui Liu; Wenkai Zhang; Zhishan Bo (Chemical Engineering Journal, 2023)

Mapping of suitable habitats for earthworms in China - Xiaoliang Li; Kening Wu; Shiheng Hao; Long Kang; Jinliang Ma; Ran Zhao; Yue Zhang (Soil Biology and Biochemistry, 2023)

Bioelectret poly(lactic acid) membranes with simultaneously enhanced physical interception and electrostatic adsorption of airborne PM0.3 - Han Shang; Keke Xu; Tian Li; Hao-Ran Yang; Jiefeng Gao; Shihang Li; Jintuo Zhu; Xinjian He; Shenghui Zhang; Huan Xu; Baolong Shen (Journal of Hazardous Materials, 2023)

Design and operation insights concerning a pilot-scale S0-driven autotrophic denitrification packed-bed process - Yi-Lu Sun; Zhuo-Ran Li; Xue-Ning Zhang; Heng Dong; Zhi-Min Qian; Shan Yi; Wei-Qin Zhuang; Hao-Yi Cheng; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Fog event is possibly a source rather than a sink of atmospheric nitrate aerosols: Insights from isotopic measurements in Nanjing, China - Hao-Ran Yu; Yan-Lin Zhang; Fang Cao; Zhu-Yu Zhao; Mei-Yi Fan; Xiao-Ying Yang (Applied Geochemistry, 2023)

Microbial electrochemical technologies assisted nitrogen recovery from different wastewater sources: Performance, life cycle assessment, and challenges - Siyuan Zhai; Dexin Zhang; Wenzong Liu; Bo Wang; Bin Liang; Chengyan Liu; Ran Zeng; Yanan Hou; Hao-Yi Cheng; Aijie Wang (Resources, Conservation and Recycling, 2023)

Long-term probabilistic streamflow forecast model with “inputs–structure–parameters” hierarchical optimization framework - Ran Mo; Bin Xu; Ping-an Zhong; Yuanheng Dong; Han Wang; Hao Yue; Jian Zhu; Huili Wang; Guoqing Wang; Jianyun Zhang (Journal of Hydrology, 2023)

Three-dimensional macroporous structure and surface carbon-coating modification of stainless-steel anode boost bioelectrocatalytic performance - Cheng-Yan Liu; Hao-Yi Cheng; Si-Yuan Zhai; Ran Zeng; De-Xin Zhang; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Alpha-ketoglutarate alleviates cadmium-induced inflammation by inhibiting the HIF1A-TNFAIP3 pathway in hepatocytes - Yinzhao Jia; Chuanzheng Yin; Wenbo Ke; Jing Liu; Bing Guo; Xiaofei Wang; Peng Zhao; Shaobo Hu; Chen Zhang; Xuan Li; Ran Liu; Xichuan Zheng; et al. (Science of The Total Environment, 2023)

Nitrogen Alleviated the Deterioration of Rice Quality by Affecting the Accumulation of Grain Storage Protein Under Elevated Temperature - Yufei Zhao; Xuan Ran; Tongyang Yin; Hao Guo; Xiaoyang Zhang; Yingying Shen; Wenzhe Liu; Yanfeng Ding; She Tang (Journal of Plant Growth Regulation, 2023)

Understanding the shortboard of regional sustainable development: fairness and efficiency of rural public resource allocation in China - Sheng Zhang; Ge Li; Ran Yu; Yuanhua Chang; Yifu Yang; Qihao Zhang; Weining Liu; Jiming Hao (Environment, Development and Sustainability, 2023)

A compound of paraprobiotic and postbiotic derived from autochthonous microorganisms improved growth performance, epidermal mucus, liver and gut health and gut microbiota of common carp (Cyprinus carpio) - Delong Meng; Qiang Hao; Qingshuang Zhang; Zhe Yu; Shubin Liu; Yalin Yang; Chao Ran; Zhen Zhang; Zhigang Zhou (Aquaculture, 2023)

Alkyl halide formation from degradation of carboxylic acids in the presence of Fe(III) and halides under light irradiation - Xueling Bai; Qian Yang; Yang Guo; Baoqiang Hao; Renyuan Zhang; Ran Duan; Jing Li (Water Research, 2023)

Airborne PM2.5 pollution: A double-edged sword modulating hepatic lipid metabolism in middle-aged male mice - Renjie Hu; Lu Zhang; Li Qin; Hao Ding; Ran Li; Weijia Gu; Rucheng Chen; Yunhui Zhang; Sanjay Rajagoplan; Kezhong Zhang; Qinghua Sun; Cuiqing Liu (Environmental Pollution, 2023)

Efficient catalytic oxidation of chlorinated volatile organic compounds over RuO2-WOx/Sn0.2Ti0.8O2 catalysts: Insight into the Cl poisoning mechanism of acid sites - Feiyi Zhou; Qi Xin; Yujie Fu; Zhesheng Hua; Yi Dong; Mingchu Ran; Hao Song; Shaojun Liu; Ruiyang Qu; Yang Yang; Xiao Zhang; Chenghang Zheng; et al. (Chemical Engineering Journal, 2023)

A new cyclopentenone derivative from Trichoderma atroviride HH-01 - Li Zhu; Jia-Peng Wang; Feng Hao; Dong Gan; Xiao-Ran Zhang; Chen-Zhe Li; Cheng-Yao Wang; Liang Zhang; Le Cai (Natural Product Research, 2023)

Time to reconsider the enigmatic tail of eastern Paleo-Tethys: New insights from Borneo - Xiao Ran Zhang; Sun-Lin Chung; Azman A. Ghani; Rezal Rahmat; Yi-Ju Hsin; Hao-Yang Lee; Ping-Ping Liu; Jinyu Xi (Lithos, 2023)

The positive effects of postbiotic (SWF concentration®) supplemented diet on skin mucus, liver, gut health, the structure and function of gut microbiota of common carp (Cyprinus carpio) fed with high-fat diet - Zhe Yu; Qiang Hao; Shu-Bin Liu; Qing-Shuang Zhang; Xing-Yu Chen; Sheng-Hui Li; Chao Ran; Ya-Lin Yang; Tsegay Teame; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2023)

The eradication of biofilm for therapy of bacterial infected chronic wound based on pH-responsive micelle of antimicrobial peptide derived biodegradable microneedle patch - Xiao-Ling Lei; Kai Cheng; Yong Li; Zi-Tao Zhong; Xiao-Lin Hou; Lai-Bo Song; Fang Zhang; Jian-Hao Wang; Yuan-Di Zhao; Qiu-Ran Xu (Chemical Engineering Journal, 2023)

Effects of demineralization mode and particle size of allogeneic bone powder on its physical and chemical properties - Kun-xiu Song; Shao-lin Ji; Yong-jie Zhao; Hao-ran Zhang; Rong-xing Ma; Jing-yu Zhang; Yong-cheng Hu (Cell and Tissue Banking, 2023)

Glucose-responsive mesoporous prussian blue nanoprobes coated with ultrasmall gold and manganese dioxide for magnetic resonance imaging and enhanced antitumor therapy - Yuehua Shi; Yu Shi; Zhaoyang Wang; Jiahe Zhang; Ran Hao; Gangwan Zhang; Xiaolong Zhao; Leyong Zeng (Chemical Engineering Journal, 2023)

Intermittent ultrasound retains cellulases unlock for enhanced cellulosic ethanol with high-porosity biochar for dye adsorption using desirable rice mutant straw - Zhen Hu; Qian Li; Yuanyuan Chen; Tianqi Li; Youmei Wang; Ran Zhang; Hao Peng; Hailang Wang; Yanting Wang; Jingfeng Tang; Muhammad Nauman Aftab; Liangcai Peng (Bioresource Technology, 2023)

Nuclease treatment enhances the probiotic effect of Bacillus velezensis T23 on hepatic steatosis and inflammation induced by high-fat diet in zebrafish - Fengli Zhang; Yinyin Luan; Qiang Hao; Qingshuang Zhang; Yalin Yang; Chao Ran; Zhen Zhang; Zhigang Zhou (Aquaculture, 2023)

Strengthening ion uptake and mitigating volume change via bimetallic telluride heterojunction for ultrastable K-ion hybrid capacitors - Zhihan Zeng; Wenqi Zhang; Hao Ma; Yuyang Yi; Xueyu Lian; Xianzhong Yang; Ran Cai; Wen Zhao; Jingyu Sun (Chemical Engineering Journal, 2023)

Machine Learning-Enabled Determination of Diffuseness of Brain Arteriovenous Malformations from Magnetic Resonance Angiography - Yuming Jiao; Jun-Ze Zhang; Qi Zhao; Jia-Qi Liu; Zhen-Zhou Wu; Yan Li; Hao Li; Wei-Lun Fu; Jian-Cong Weng; Ran Huo; Shao-Zhi Zhao; Shuo Wang; et al. (Translational Stroke Research, 2022)

Evaluation of ionospheric-constrained single-frequency PPP enhanced with an improved stochastic model - Hang Shen; Shuhui Li; Lihua Li; Wenjie Zhang; Yu Tian; Wenyi Hao; Ran Li (Earth Science Informatics, 2022)

Tracking Neural Stem Cells in vivo: Achievements and Limitations - Chun-Ran Xue; Kan Wang; Meng-Ze Zhang; Ze Wang; Ya-Ying Song; Hao-Jun Yu; Yong Hao; Yang-Tai Guan (Stem Cell Reviews and Reports, 2022)

Genome-wide association analysis of root length traits in Brassica napus at germination stage under sodium carbonate stress - Jindong Chen; Hao Zhang; Jiangqun Tong; Chunyue Liu; Jinghong Ran; Juan Tang; Jiaying Liu; Jing Wen; Changli Zeng; Heping Wan; Jinxiong Shen (Euphytica, 2021)

Roles of Iron Limitation in Phytoplankton Dynamics in the Western and Eastern Subarctic Pacific - Hao-Ran Zhang; Yuntao Wang; Peng Xiu; Yiquan Qi; Fei Chai (Frontiers in Marine Science, 2021)
The subarctic Pacific is one of the major high-nitrate, low-chlorophyll (HNLC) regions where marine productivity is greatly limited by the supply of iron (Fe) in the region. There is a distinct seasonal difference in the chlorophyll concentrations of the east and west sides of the subarctic Pacific because of the differences in their driving mechanisms. In the western subarctic Pacific, two chlorophyll concentration peaks occur: the peak in spring and early summer is dominated by diatoms, while the peak in late summer and autumn is dominated by small phytoplankton. In the eastern subarctic Pacific, a single chlorophyll concentration peak occurs in late summer, while small phytoplankton dominate throughout the year. In this study, two one-dimensional (1D) physical–biological models with Fe cycles were applied to Ocean Station K2 (Stn. K2) in the western subarctic Pacific and Ocean Station Papa (Stn. Papa) in the eastern subarctic Pacific. These models were used to study the role of Fe limitation in regulating the seasonal differences in phytoplankton populations by reproducing the seasonal variability in ocean properties in each region. The results were reasonably comparable with observational data, i.e., cruise and Biogeochemical-Argo data, showing that the difference in bioavailable Fe (BFe) between Stn. K2 and Stn. Papa played a dominant role in controlling the respective seasonal variabilities of diatom and small phytoplankton growth. At Stn. Papa, there was less BFe, and the Fe limitation of diatom growth was two times as strong as that at Stn. K2; however, the difference in the Fe limitation of small phytoplankton growth between these two regions was relatively small. At Stn. K2, the decrease in BFe during summer reduced the growth rate of diatoms, which led to a rapid reduction in diatom biomass. Simultaneously, the decrease in BFe had little impact on small phytoplankton growth, which helped maintain the relatively high small phytoplankton biomass until autumn. The experiments that stimulated a further increase in atmospheric Fe deposition also showed that the responses of phytoplankton primary production in the eastern subarctic Pacific were stronger than those in the western subarctic Pacific but contributed little to primary production, as the Fe limitation of phytoplankton growth was replaced by macronutrient limitation.

Correction to: Experimental study on strength properties, fracture patterns, and permeability behaviors of sandstone containing two filled fissures under triaxial compression - Tingchun Li; Yiteng Du; Qingwen Zhu; Jinlin Ran; Hao Zhang; Xueyang Xing (Bulletin of Engineering Geology and the Environment, 2021)

Experimental study on strength properties, fracture patterns, and permeability behaviors of sandstone containing two filled fissures under triaxial compression - Tingchun Li; Yiteng Du; Qingwen Zhu; Jinlin Ran; Hao Zhang; Xueyang Xing (Bulletin of Engineering Geology and the Environment, 2021)

KCNQ Channels in the Mesolimbic Reward Circuit Regulate Nociception in Chronic Pain in Mice - Hao-Ran Wang; Su-Wan Hu; Song Zhang; Yu Song; Xiao-Yi Wang; Lei Wang; Yang-Yang Li; Yu-Mei Yu; He Liu; Di Liu; Hai-Lei Ding; Jun-Li Cao (Neuroscience Bulletin, 2021)
Mesocorticolimbic dopaminergic (DA) neurons have been implicated in regulating nociception in chronic pain, yet the mechanisms are barely understood. Here, we found that chronic constructive injury (CCI) in mice increased the firing activity and decreased the KCNQ channel-mediated M-currents in ventral tegmental area (VTA) DA neurons projecting to the nucleus accumbens (NAc). Chemogenetic inhibition of the VTA-to-NAc DA neurons alleviated CCI-induced thermal nociception. Opposite changes in the firing activity and M-currents were recorded in VTA DA neurons projecting to the medial prefrontal cortex (mPFC) but did not affect nociception. In addition, intra-VTA injection of retigabine, a KCNQ opener, while reversing the changes of the VTA-to-NAc DA neurons, alleviated CCI-induced nociception, and this was abolished by injecting exogenous BDNF into the NAc. Taken together, these findings highlight a vital role of KCNQ channel-mediated modulation of mesolimbic DA activity in regulating thermal nociception in the chronic pain state.

A Highly Selective Turn‐on Fluorescent and Naked‐eye Colourimetric Dual‐channel Probe for Cyanide Anions Detection in Water Samples - Ya Wu; Wen-Min Ding; Juan Li; Geng Guo; Shu-Zhen Zhang; Hao-Ran Jia; Yin-Xia Sun (Journal of Fluorescence, 2021)

Estimation of the longitudinal dispersion coefficient using a two-zone model in a channel partially covered with artificial emergent vegetation - Jiao Zhang; Wen-Xin Huai; Hao-Ran Shi; Wei-Jie Wang (Environmental Fluid Mechanics, 2021)

Cerebellar Atrophy in Multiple System Atrophy (Cerebellar Type) and Its Implication for Network Connectivity - Hao Zhang; Shaozhen Ji; Shan Ren; Ming Liu; Weizheng Ran; Xinning Zhang; Wenyang Tian; Zhigang Chen; Zhiqun Wang (The Cerebellum, 2020)

Innovative health risk assessments of heavy metals based on bioaccessibility due to the consumption of traditional animal medicines - Tian-Tian Zuo; Hao-Ran Qu; Hong-Yu Jin; Lei Zhang; Fei-Ya Luo; Kun-Zi Yu; Fei Gao; Qi Wang; Lei Sun; Huai-Zhen He; Shuang-Cheng Ma (Environmental Science and Pollution Research, 2020)

AUV 3D Path Planning Based on the Improved Hierarchical Deep Q Network - Yushan Sun; Xiangrui Ran; Guocheng Zhang; Hao Xu; Xiangbin Wang (Journal of Marine Science and Engineering, 2020)
This study proposed the 3D path planning of an autonomous underwater vehicle (AUV) by using the hierarchical deep Q network (HDQN) combined with the prioritized experience replay. The path planning task was divided into three layers, which realized the dimensionality reduction of state space and solved the problem of dimension disaster. An artificial potential field was used to design the positive rewards of the algorithm to shorten the training time. According to the different requirements of the task, this study modified the rewards in the training process to obtain different paths. The path planning simulation and field tests were carried out. The results of the tests corroborated that the training time of the proposed method was shorter than that of the traditional method. The path obtained by simulation training was proved to be safe and effective.

Terrestrial N 2 O emissions and related functional genes under climate change: A global meta‐analysis - Linfeng Li; Zhenzhen Zheng; Weijin Wang; Joel A. Biederman; Xingliang Xu; Qinwei Ran; Ruyan Qian; Cong Xu; Biao Zhang; Fang Wang; Shutong Zhou; Lizhen Cui; et al. (Global Change Biology, 2020)
Nitrous oxide (N 2 O) emissions from soil contribute to global warming and are in turn substantially affected by climate change. However, climate change impacts on N 2 O production across terrestrial ecosystems remain poorly understood. Here, we synthesized 46 published studies of N 2 O fluxes and relevant soil functional genes (SFGs, that is, archaeal amoA , bacterial amoA , nosZ , narG , nirK and nirS ) to assess their responses to increased temperature, increased or decreased precipitation amounts, and prolonged drought (no change in total precipitation but increase in precipitation intervals) in terrestrial ecosystem (i.e. grasslands, forests, shrublands, tundra and croplands). Across the data set, temperature increased N 2 O emissions by 33%. However, the effects were highly variable across biomes, with strongest temperature responses in shrublands, variable responses in forests and negative responses in tundra. The warming methods employed also influenced the effects of temperature on N 2 O emissions (most effectively induced by open‐top chambers). Whole‐day or whole‐year warming treatment significantly enhanced N 2 O emissions, but daytime, nighttime or short‐season warming did not have significant effects. Regardless of biome, treatment method and season, increased precipitation promoted N 2 O emission by an average of 55%, while decreased precipitation suppressed N 2 O emission by 31%, predominantly driven by changes in soil moisture. The effect size of precipitation changes on nirS and nosZ showed a U‐shape relationship with soil moisture; further insight into biotic mechanisms underlying N 2 O emission response to climate change remain limited by data availability, underlying a need for studies that report SFG. Our findings indicate that climate change substantially affects N 2 O emission and highlights the urgent need to incorporate this strong feedback into most climate models for convincing projection of future climate change.

Three-Dimensional Path Tracking Control of Autonomous Underwater Vehicle Based on Deep Reinforcement Learning - Yushan Sun; Chenming Zhang; Guocheng Zhang; Hao Xu; Xiangrui Ran (Journal of Marine Science and Engineering, 2019)
In this paper, the three-dimensional (3D) path tracking control of an autonomous underwater vehicle (AUV) under the action of sea currents was researched. A novel reward function was proposed to improve learning ability and a disturbance observer was developed to observe the disturbance caused by currents. Based on existing models, the dynamic and kinematic models of the AUV were established. Deep Deterministic Policy Gradient, a deep reinforcement learning, was employed for designing the path tracking controller. Compared with the backstepping sliding mode controller, the controller proposed in this article showed excellent performance, at least in the particular study developed in this article. The improved reward function and the disturbance observer were also found to work well with improving path tracking performance.

Design and Experiment of a Plateau Data-Gathering AUV - Hao Xu; Guo-Cheng Zhang; Yu-Shan Sun; Shuo Pang; Xiang-Rui Ran; Xiang-Bin Wang (Journal of Marine Science and Engineering, 2019)
The design, control, and implementation of an autonomous underwater vehicle (AUV) for collecting hydrological information from plateau rivers and lakes are presented in this paper. The hardware and software structures of the control system were previously described. A novel sliding mode controller (SMC) with combinational reaching law of vertical hovering motion is proposed to improve the robustness and stability. The S-plane control, a nonlinear controller with little parameters, is used in the horizontal motion. Besides, the navigation strategy based on the dead-reckoning algorithm, a path tracking based on the light-of-sight (LOS) algorithm, and a control allocation strategy considering saturation are present. Finally, experiments were performed in a tank and in a river in the Qinghai–Tibet Plateau to prove the feasibility and reliability of the AUV system.

A Case of Chromoblastomycosis Caused by Fonsecaea Pedrosoi and Investigation of the Pathogenic Fungi - Ruifeng Zhang; Yuping Ran; Hao Zhang; Yaling Dai; Xin Ran; Chaoliang Zhang; Wei Qin; Liyan Xi (Mycopathologia, 2019)

Trends of sea surface temperature and sea surface temperature fronts in the South China Sea during 2003–2017 - Yi Yu; Hao-Ran Zhang; Jiangbo Jin; Yuntao Wang (Acta Oceanologica Sinica, 2019)

Effect of LSU and ITS genetic markers and reference databases on analyses of fungal communities - Chao Xue; Yuewen Hao; Xiaowei Pu; C. Ryan Penton; Qiong Wang; Mengxin Zhao; Bangzhou Zhang; Wei Ran; Qiwei Huang; Qirong Shen; James M. Tiedje (Biology and Fertility of Soils, 2019)

A genome-wide association study on growth traits in orange-spotted grouper (Epinephelus coioides) with RAD-seq genotyping - Hui Yu; Xinxin You; Jia Li; Xinhui Zhang; Shuai Zhang; Shoujia Jiang; Xueqiang Lin; Hao-Ran Lin; Zining Meng; Qiong Shi (Science China Life Sciences, 2018)

Characterization, Cytotoxicity, and Genotoxicity of TiO2 and Folate-Coupled Chitosan Nanoparticles Loading Polyprenol-Based Nanoemulsion - Ran Tao; Chengzhang Wang; Changwei Zhang; WenJun Li; Hao Zhou; Hongxia Chen; Jianzhong Ye (Biological Trace Element Research, 2018)

Global mapping of artificial surfaces at 30-m resolution - XueHong Chen; Xin Cao; AnPing Liao; LiJun Chen; Shu Peng; Miao Lu; Jin Chen; WeiWei Zhang; HongWei Zhang; Gang Han; Hao Wu; Ran Li (Science China Earth Sciences, 2016)

Exendin-4 Enhances Motor Function Recovery via Promotion of Autophagy and Inhibition of Neuronal Apoptosis After Spinal Cord Injury in Rats - Hao-Tian Li; Xing-Zhang Zhao; Xin-Ran Zhang; Gang Li; Zhi-Qiang Jia; Ping Sun; Ji-Quan Wang; Zhong-Kai Fan; Gang Lv (Molecular Neurobiology, 2016)

Evolution of the microbial community of the biofilm in a methane-based membrane biofilm reactor reducing multiple electron acceptors - Ran Chen; Yi-Hao Luo; Jia-Xian Chen; Yin Zhang; Li-Lian Wen; Ling-Dong Shi; Youneng Tang; Bruce E. Rittmann; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2016)

Depositional environment and micropore characteristics of the Ediacaran Doushantuo Formation black shale in Western Hubei, China - Hao Wang; Ziquan Yong; Xuan Zhang; Bo Ran; Di Yang; Chao Luo; Bin Deng (Arabian Journal of Geosciences, 2016)

Subliminal trauma reminders impact neural processing of cognitive control in adults with developmental earthquake trauma: a preliminary report - Xue Du; Yu Li; Qian Ran; Pilyoung Kim; Barbara L. Ganzel; GuangSheng Liang; Lei Hao; Qinglin Zhang; Huaqing Meng; Jiang Qiu (Experimental Brain Research, 2016)

Genome-wide characterization and analysis of F-box protein-encoding genes in the Malus domestica genome - Hao-Ran Cui; Zheng-Rong Zhang; Wei lv; Jia-Ning Xu; Xiao-Yun Wang (Molecular Genetics and Genomics, 2015)

Reply to Shaocheng Ji’s discussion on ‘Coesite-bearing eclogite breccia: implication for coseismic ultrahigh-pressure metamorphism and the rate of the process’ by Yang et al. (Contrib. Mineral. Petrol., 2014, 167: 1013) - Jian-Jun Yang; Meng-Xi Huang; Hao-Ran Zhang; Cong Yu (Contributions to Mineralogy and Petrology, 2015)

Generalized Superficial Mycosis Caused by Trichophyton raubitschekii in China: Case Report and Review of the Literature - Hao Zhang; Xincai Xiong; Ting Liu; Yuping Ran (Mycopathologia, 2015)

Estimation of quality factors by energy ratio method - Zong-Jun Wang; Si-Yuan Cao; Hao-Ran Zhang; Ying-Ming Qu; Dian Yuan; Jin-Hao Yang; Guan-Ming Shao (Applied Geophysics, 2015)

Recycling of sediment into the mantle source of K-rich mafic rocks: Sr–Nd–Hf–O isotopic evidence from the Fushui complex in the Qinling orogen - Hao Wang; Yuan-Bao Wu; Chao-Ran Li; Tian-Yu Zhao; Zheng-Wei Qin; Liu-Qin Zhu; Shan Gao; Jian-Ping Zheng; Xiao-Ming Liu; Lian Zhou; Yang Zhang; Sai-Hong Yang (Contributions to Mineralogy and Petrology, 2014)

Mucor irregularis Infection Around the Inner Canthus Cured by Amphotericin B: A Case Report and Review of Published Literatures - Daoxian Kang; Xian Jiang; Huiying Wan; Yuping Ran; Dan Hao; Chaoliang Zhang (Mycopathologia, 2014)

Coesite-bearing eclogite breccia: implication for coseismic ultrahigh-pressure metamorphism and the rate of the process - Jian-Jun Yang; Meng-Xi Huang; Qian-Yi Wu; Hao-Ran Zhang (Contributions to Mineralogy and Petrology, 2014)

Analysis of quality factors for Rayleigh channel waves - Xiao-Hui Yang; Si-Yuan Cao; De-Chun Li; Peng-Fei Yu; Hao-Ran Zhang (Applied Geophysics, 2014)

Identification of Malassezia Species in Patients with Seborrheic Dermatitis in China - Hao Zhang; Yuping Ran; Zhen Xie; Ruifeng Zhang (Mycopathologia, 2013)

The impact of acid rain on China’s socioeconomic vulnerability - Yue-Jun Zhang; Hao-Ran Chang (Natural Hazards, 2012)

Endothelium-specific SIRT1 overexpression inhibits hyperglycemia-induced upregulation of vascular cell senescence - HouZao Chen; YanZhen Wan; Shuang Zhou; YunBiao Lu; ZhuQin Zhang; Ran Zhang; Feng Chen; DeLong Hao; Xiang Zhao; ZhiChen Guo; DePei Liu; ChihChuan Liang (Science China Life Sciences, 2012)

Clavispora lusitaniae and Chaetomium atrobrunneum as Rare Agents of Cutaneous Infection - Hao Zhang; Yuping Ran; Dongming Li; Yongfang Liu; Yun Xiang; Ruifeng Zhang; Yaling Dai (Mycopathologia, 2010)

Oxidative Damage of the Extracts of Condensate, Particulate and Semivolatile Organic Compounds from Gasoline Engine Exhausts on Testicles of Rats - Wangjun Che; Hong Qiu; Guiming Liu; Yun Ran; Hao Zhang; Li Zhang; Weihua Wen (Bulletin of Environmental Contamination and Toxicology, 2009)

CLOCK/BMAL1 regulates human nocturnin transcription through binding to the E-box of nocturnin promoter - Ran Li; Jiping Yue; Yu Zhang; Lan Zhou; Wei Hao; Jiangang Yuan; Boqin Qiang; Jian M. Ding; Xiaozhong Peng; Ji-Min Cao (Molecular and Cellular Biochemistry, 2008)

Rapid Evolution, Genetic Variations, and Functional Association of the Human Spermatogenesis-Related Gene NYD-SP12 - Qü Zhang; Feng Zhang; Xiao-hua Chen; Yin-qiu Wang; Wei-qi Wang; Alice A. Lin; Luca L. Cavalli-Sforza; Li Jin; Ran Huo; Jia-hao Sha; Zheng Li; Bing Su (Journal of Molecular Evolution, 2007)